A pH-responsive, kojic acid-based amphiphilic polymer as a nanocarrier for targeted herbicide delivery - Yuying Xie; Yangchun Ge; Zhuochao Shen; Yupeng Qiu; Haohua Zhang; Changmeng Sun; Jiangkuan Tang; Bingke Li; Junran Xu; Ping Liang; Yubang Tao; Shengtian Wang; et al. (Crop Protection, 2026)

Sex peptide receptor modulates sex pheromone perception plasticity in female Galleria mellonella across mating status - Zhen-Ping Guo; Xu-Dong Pang; Li-Lin Luo; Ming-Qing Yu; Jun-Hong Linghu; Hua-Yan Xie; Guy Smagghe; Tong-Xian Liu; Shun-Hua Gui (Insect Biochemistry and Molecular Biology, 2026)

Highly selective CO2/H2 separation by isomeric CALF-20-based porous slurry - Han Tang; Jin Cai; Zi-Ying Zhao; Long-Long Xie; Ping-Xiang Wang; Yang Meng; Hai-Hang Qin; Peng Xiao; Bei Liu; Yun-Lei Peng; Chang-Yu Sun; Zhi Li; et al. (Chemical Engineering Journal, 2026)

Synthesis and valorization of corn silk-derived carbon dots for antimicrobial fruit preservation - Yong-Ping Wen; Meng-Ting Wu; Kwang-Pyo Kim; Meng-Yi Chen; Jia-Hui Liu; Ya-Ping Li; An-Guo Wu; Xiang Li; Song-Zhi Xie; Die Gao; Jian-Ming Wu; Xiao-Gang Zhou (International Journal of Food Microbiology, 2026)

Boosting lattice oxygen activation and active sites generation via an Mn-O electron bridge for efficient simultaneous oxidation of toluene and NO over Mn5Co4Ce3Ox catalyst - Lei Gao; Yukai Quan; Ping Fang; Dong Xie; Caiting Li; Cheng Sun; Jiahao Zhang; Ruotao Bai; Jingshuo Zhang (Fuel, 2026)

A non-complex-algorithmic and manually calculable fragment-resolved isotope framework ratios for geographic authentication of refined sugar - ShuoCong Li; ZhenPeng Zhen; XiaoFeng Xie; RongWei Fu; DeJin Kong; Zhu Lin; ZhaoHua Ping; GuiHua Wang; YuFeng Gao (Food Chemistry, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Erosion and entrainment in dry granular flows: Insights from large-scale experiments - Shi-lin Zhang; Yang Gao; Yue-ping Yin; Lonneke Roelofs; Wen-pei Wang; Xie-wen Hu; Bin Li (Engineering Geology, 2026)

Indian monsoon regulates the sediment supply of the Upper Yangtze River since ∼2 Ma - Xudong Zhao; Taylor F. Schildgen; Huiping Zhang; Weitao Wang; Yan Ma; Ping Wang; Yarong Zhang; Yifei Li; Chaopeng Li; Hongseng Xie; Peizhen Zhang (Earth and Planetary Science Letters, 2026)

Unlocking multiscale structure-property relationships in epoxy thermosets: A machine learning-driven approach to superior multi-objective performance - Gaoming Li; Yeping Wu; Yujie Xie; Chunhua Zhu; Song Yao; Zhongtao Chen; Ping Zhang; Zixuan Luo; Xiuli Zhao; Sixun Zheng; Yinyu Zhang (Chemical Engineering Journal, 2026)

Hierarchical core–shell nanoplatforms based on sacrificial template-directed ZnO2@ZIF-8 for spatiotemporally controlled and self-augmented chemodynamic–photothermal antibacterial therapy - Yi-Fei Hui; Duan-Ping Hu; Yi Zhao; Shulin Li; Zhi-Feng Cai; Lin-Yi Li; Yuming Xie; Yong-Nian Zeng; Zu-Jin Lin; Fa-Qiang Tang (Chemical Engineering Journal, 2026)

A tea exosome-integrated self‑oxygenating cascade chitosan/oxidized alginate hydrogel for remodeling the hyperglycemic and hypoxic microenvironment in diabetic wound healing - Li-Hua Xie; Xin-Hui Zhou; Wei-Qiu Wen; Wei Wang; Ping Gui; Li Li; Guan-Hai Wang (Carbohydrate Polymers, 2026)

Chemical constituents from Micromeria biflora and their chemotaxonomic significance - Chen Peng; Xing-Li Zhang; Deng-Li Xiong; Fei-Yan Zhao; Kun Xie; Hong-Ping He; Ming-Ming Li (Biochemical Systematics and Ecology, 2026)

How well do reanalysis datasets capture the onset dates of extreme temperature events in China? - Ping Zhou; Yan Wu; Zexiang Li; Yawen Yang; Chuchu Zhang; Dan Li; Shuishi Xie; Liangqing Wu; Keyuan Zhong (Meteorology and Atmospheric Physics, 2026)

Fipronil and its metabolites in a tropical estuary: multi-compartment distribution, trophic transfer, and risk assessment - Yu-Han Xie; Can Huo; Zhi-Yan Wang; Shan-Shan Yao; Heng-Xiang Li; Yu Zhong; Xiao-Ping Huang; Xiang-Rong Xu (Marine Environmental Research, 2026)

From bacterial template to green catalyst: Bio-fabrication of nanostructured nickel hydroxycarbonate for oxygen evolution via microbial mineralization - Feng Duan; Qichang Li; Li Xu; Haifang Wu; Ercai Pan; Wei Ding; Junhui Guo; Hang Ping; Liuyi Zhao; Hao Xie; Zhengyi Fu; Zhaoyong Zou (Chemical Engineering Journal, 2026)

Intravenous Exposure to Amino-polystyrene Induces Excessive Autophagy and Apoptosis in Myocardium Through ROS Driven PI3K/AKT/mTOR Axis - Wen Gou; Yujun Xie; Rui Xia; Ping Gou; Chunfeng Cao; Fujun Luan; Beizhong Liu; Yuan Li (Cardiovascular Toxicology, 2026)

Effects of fish meal replacement with bullfrog skin meal on growth performance, muscle quality, and hepatointestinal health in grass carp, Ctenopharyngodon idella - Jingjing Tian; Yongjie Ma; Ping Wang; Mengmeng Ji; Yun Xia; Kai Zhang; Hongyan Li; Wangbao Gong; Zhifei Li; Wenping Xie; Quanfa Zhong; Guangjun Wang; et al. (Animal Feed Science and Technology, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

An innovative immobilization-free homogeneous electrochemical strategy facilitated by buoyancy -magnetism separation for evaluating the acetamiprid in food - Ya-Rong Xie; Yue-Han Wang; Jia-Le Wang; Li-Ping Jia; Wei Zhang; Lei Shang; Xiao-Jian Li; Qing-Wang Xue; Huai-Sheng Wang; Rong-Na Ma (Food Chemistry, 2026)

Benzophenone-2 disrupts craniofacial cartilage development via esr2a-Dependent inhibition of endothelin signaling in zebrafish larvae - Zhuoyi Xie; Keying Li; Xiaomai Zhou; Qiuchen Wu; Xiangrong Zhou; Ping Zeng; Jing Li; Qiao Niu; Zhipeng Qi; Xinying Zhao; Weiyi Song (Environmental Research, 2026)

Early Miocene Populus L. Fossils Reveal the Northwestward Expansion of the East Asian Summer Monsoon Into Eastern Qaidam - Zhen‐Dong Cao; San‐Ping Xie; Jing‐Nan Huang; Yun‐Zhe Zhang; Zi‐Yi Li; Si‐Hang Zhang; De‐Fei Yan (Journal of Biogeography, 2026)
Aim The evolution of the East Asian Summer Monsoon (EASM) is critical for understanding Asian biodiversity and ecosystem stability. While models and geological records suggest the EASM reached the Qaidam Basin during the Miocene, macrofossil evidence remains scarce. We aimed to test the hypothesis of a northwestward monsoon expansion using newly discovered Populus fossils as bioclimatic indicators. Location Wulan Basin, northeastern Tibetan Plateau, Qinghai Province, China. Taxon Angiosperms (Salicaceae: Populus L.). Methods We conducted morphological analyses on leaf fossils and identified their Nearest Living Relative (NLR). By establishing correlations between the leaf traits of the NLR and modern climatic factors, we reconstructed the paleoclimate of the Wulan Basin. Furthermore, we employed Species Distribution Modelling (MaxEnt) to simulate the potential range of this lineage under Early Miocene conditions to explore monsoon‐driven habitat shifts. Results The late Early Miocene fossils from the Wulan Basin are morphologically most similar to the extant Populus davidiana , a species characteristic of temperate, semi‐humid environments. The presence of this lineage indicates that the Wulan Basin—currently an arid region—experienced significantly higher precipitation and a temperate semi‐humid climate during the Early Miocene. MaxEnt modelling reveals that the suitable bioclimatic envelope for this Populus group extended much further northwest than its modern range, providing a potential biological signal of enhanced moisture transport into the interior of East Asia. Main Conclusions The occurrence of Populus fossils in the Wulan Basin provides a preliminary biological indicator for the northwestward expansion of the EASM into the northeastern Tibetan Plateau during the late Early Miocene, although corroboration from additional proxy records and localities is still needed. This climatic shift, likely driven by the phased uplift of the Tibetan Plateau, transformed the regional hydrological cycle and facilitated the migration of mesic woody taxa into Asia's interior. Our findings highlight the profound impact of tectonic‐monsoon interactions on historical plant distributions.

Shift of nitrogen metabolism drives the evolution of multidrug resistance in wastewater microbiomes under long-term fluoride stress - Yun-Tian He; Fei Wang; Shu-Yu Yu; Chen-Xin Xie; Li Yuan; Zheng-Hao Li; Guo-Ping Sheng (Water Research, 2026)

n-butanol treatment alleviates chilling injury of mango fruit by regulating membrane lipid metabolism - Hao Dong; Ping Yi; Lihong Xie; Qi Wei; Yuhan Long; Min Huang; Ting Gan; Qiuyu Cheng; Lan Zhang; Li Li; Jian Sun (Postharvest Biology and Technology, 2026)

Evolution of trade-offs and synergies of ecohydrological services under vegetation restoration - Ping Li; Zhan Xie; Wenqian Liu; Zhipeng Zhu (Ecological Engineering, 2026)

Limosilactobacillus reuteri LR-99 Modulates Gut Microbiota and Core Symptoms in Children with Autism Spectrum Disorder: A Single-arm Pilot Study - Kai Gong; Ziying Xie; Ping Zhang; Jing Xu; Jiangfeng Huang; Xingyu Li; Lihong Huang (Probiotics and Antimicrobial Proteins, 2026)

Ankyrin-repeat transmembrane protein WAI-1 confers multiple disease resistance in wheat by activating autoimmunity - Qiuhong Wu; Wenling Li; Yongxing Chen; Huaizhi Zhang; Delin Li; Zhan Li; Fei Xiong; Guanghao Guo; Lei Dong; Xuejia Cui; Jingzhong Xie; Ping Lu; et al. (Science China Life Sciences, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

First fossil fruit of Spatholobus (Papilionoideae, Fabaceae) from East Asia - Yi-Shan Zhao; Zhen-Dong Cao; Jing-Nan Huang; Zi-Yi Li; Torsten Wappler; Zhen-Xian Zhang; Shu-mei Xiao; Wei-Yu-Dong Deng; San-Ping Xie (Review of Palaeobotany and Palynology, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Paleoseismic activity revealed from soft sediment deformation structures in the Eastern Himalayan Syntaxis since the Last Glacial Maximum - Huiying Wang; Ping Wang; Gang Hu; Zinan Zou; Wenqiao Li; Chao Xie (Journal of Asian Earth Sciences, 2026)

Structural characterization and antitumor activity via immune modulation of an α-glucan from Grifola frondosa - Hui-Xiang Tian; Qin-Zhao Ruan; Yi-Zhen Xie; Wei Chen; Chun Xiao; Wei Zhong; Yuan-Chao Liu; Shao-Dan Chen; Tian-Qiao Yong; Hui-Ping Hu; Xiang-Min Li; Qing-Ping Wu (Carbohydrate Polymers, 2026)

Sedative effects and stress-alleviating capabilities of four dietary plant-derived compounds on Procambarus clarkii - Zihao Li; Xinyi Xie; Ziqian Sun; Zhaoxuan Zhu; Shuang Zhang; Xiaoyan Liang; Mengyu Teng; Haitang Wang; Xiuhong Liu; Ping Yang; Xingxing Fang (Veterinary Research Communications, 2026)

High-quality genome of guar (Cyamopsis tetragonoloba) provides the new insights into the biosynthesis and origination of galactomannans in Fabaceae family - Yuanhao Ding; Xinglong Zhao; Hui Yao; Shicai Huang; Xuyao Wang; Yayu Chen; Ping Li; Chengzhi Xie; Jiaquan Huang; Zhuang Yang; Haiyan Hu (Plant Cell Reports, 2026)

Caffeic acid restores neurogenesis and synaptic integrity under glucolipotoxic stress by suppressing inflammation and pyroptosis - I-Ning Tsai; Xiang-Ning Xie; Ping-En Ko; Yung-Che Tsai; Ching-Chun Chen; Li-Sung Hsu; Chau-Jong Wang (Metabolic Brain Disease, 2026)

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

Microscopic Hydraulic–Mechanical Coupling Fracturing Behavior and Failure Mechanisms of Reservoir Rocks - Zhi Zhao; Zhi-Hong Li; Yun-Gang Duan; Liang-Fu Xie; Zheng Li; Guo-Feng Yu; Xiao-Ping Zhou (Rock Mechanics and Rock Engineering, 2026)

New cutting tool wear testing method for evaluating the influence of foam additive on plowing effect during shield TBM tunnelling in dense sandy gravel ground - Shao-Hui Tang; Xiao-Ping Zhang; Quan-Sheng Liu; Yu-Cong Pan; Wei-Qiang Xie; Xin-Fang Li; Hao-Jie Wang (Tunnelling and Underground Space Technology, 2026)

Production of eggshell-polypyrrole composites for enhanced Cr (VI) removal from wastewater: Mechanisms and optimization - Jiayin Xie; Size Li; Xinru Yang; Xueming Qin; Ping Sun; Lve Shi; Hongmin Li; Yongsheng Zhao (Journal of Water Process Engineering, 2026)

Characteristics of structural superimposed halo at the Jiawula Ag-Pb-Zn deposit, Inner Mongolia, China and its significance for exploration - Xin-yu Gao; Gui-yuan Sun; Kang Wang; Wei Zhang; Zhi-ping Li; Wen-ju Li; Jiang Wei; Lin Yang; Hong-zhe Xie; Zi-wen Yang; Chao Ma (Journal of Geochemical Exploration, 2026)

Ecological lock-in and functional mismatch in abandoned coastal ponds: mechanisms and management implications - Yi'na Li; Yanzi Cai; Junjun Bai; Ying Man; Dongxue Li; Qing Wang; Yujia Zhai; Ping Qi; Tian Xie; Baoshan Cui (Journal of Environmental Management, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

A downscaling method for CMIP6 precipitation based on the Bayesian ridge spatiotemporal weighted regression model - Jiawen Yu; Ping Duan; Mingguo Wang; Wenbin Xie; Jia Li; Ying Xia (Climate Dynamics, 2026)

Efficient depolymerization of polystyrene waste into styrene monomers over the microwave-assisted Zn/b-ZnO catalyst system - Zijian Zhang; Bonan Liu; Li Yang; Jingwen Wang; Yuqing Dong; Chao Tang; Ping Wang; Haijiao Xie; Lei Zhang; Lu Zhang; Jun Zhao; Yu Fan; et al. (Journal of Environmental Chemical Engineering, 2026)

Upgrading oxygen vacancy and reducibility for enhancing synchronous abatement of Hg0 and toluene over Co-Mn-Ce trimetallic oxides fortified biochar catalysts - Jiaqing Li; Yanyan Feng; Lei Gao; Ping Fang; Yunqing Wang; Caiting Li; Jinke Xie; Yukai Quan; Siyou Li (Journal of Environmental Chemical Engineering, 2026)

Lactic acid bacteria diversity in traditional fermented dairy products: Seasonal influences and microbial interactions - Jie Zhao; Yangbo Jiao; Ping Du; Dan Wang; Yu Li; Xin Su; Shuaili Zheng; Liang Zhou; Jiaqi Xie; Jie Yu (Food Bioscience, 2026)

In-situ tar reduction and catalytic reforming in sewage sludge gasification using steel slag oxygen carrier - Quxiu Dai; Qianrong Zhang; Nanqi Ren; Jiawei Li; Qihong Cen; Wang Du; Longgui Xie; Liping Ma; Ping Ning; Binbin He (Bioresource Technology, 2026)

The Spatiotemporal Evolution of Sugarcane Growth Based on Remote Sensing Monitoring and its Influence Factors Detection Regression Analysis in Guangxi, China - Yun-chuan Yang; Chang-zheng Wei; Xin-chang Xie; Li-ping Liao; Li-qing Liang; Zong-heng Li; Meng-dong He; Chong-xun Mo; Xun-gui Li; Gui-kai Sun (Sugar Tech, 2026)

Immobilization and magnetic removal of lead in contaminated soils using a waste-derived magnetic molecular sieve - Chang Lei; Xiu-Ru Xie; Lai-Shou Long; Rui Li; Zhi-Ping Fu; Zhi-Yue Zhao (Journal of Soils and Sediments, 2026)

Trade-offs between diversity and stability mediated by positive cohesion in sediment microbiomes under algal blooms - Ruyi Li; Jianfeng Chen; Qingyang Rao; Shangsheng Sun; Yihan Wang; Misha Zhong; Qingchuan Chou; Meng Zhang; Haojie Su; Ping Xie (Algal Research, 2026)

Drying methods impact bioactive compounds in Siraitia grosvenorii fruit: Metabolomic insights - Li Li; Lihong Xie; Ping Yi; Ting Gan; Zhenmei Fan; Min Huang; Shiqi Wang; Dan Luo; Rui Pang; Fenglai Lu; Jinfeng Sheng; Jian Sun; et al. (Food Chemistry, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Probabilistic large deformation analysis of rainfall-induced slope failures considering spatial variability of saturated hydraulic conductivity - Jian-Ping Li; Shui-Hua Jiang; Jiawei Xie; Jinsong Huang (Bulletin of Engineering Geology and the Environment, 2026)

Histone H3.3 phosphorylation facilitates H3K9me3-heterochromatin formation during retrotransposon silencing and X-chromosome inactivation via H3.3K27me3–CBX7–KAP1 axis - Jun Chen; Jiyu Chen; Zhouliang Yu; Liwei Zhang; Yanchao Liu; Xuan Ouyang; Juan Yu; Menghan Wang; Shangqiang Xie; Ming Wang; Tiantian Zhang; Zhaohui Jin; et al. (Science Bulletin, 2026)

Multi-scale rough structure membrane with switchable wettability for highly efficient oil-water separation - Meng Zhu; Xiang Li; Ying Wang; Ping Zhang; Ailin Xie; Xiaobo Gong; Yong Liu (Process Safety and Environmental Protection, 2026)

Three new matrine-type alkaloids from Sophora alopecuroides with cytotoxic activity - Yan-Ping Qiu; He Tian; Qian Xie; Shuai Li; Bi-Qian Dong; Guan-Min Su; Ding Luo; Lin-Zhao Ye (Phytochemistry Letters, 2026)

A multiscale risk operation and decision making model for inter-basin water diversion project under climate variability - Juan Chen; Zhen-ran Zhang; Yi-fan Liang; Xiao-hui Fan; Jian-qing Xie; Zhen Li; Ping-an Zhong (Environmental Research, 2026)

Whole-body RNA Sequencing Analysis of the Post-larval Reveals the Sex-biased Gene and MiRNA in the Prawn Macrobrachium rosenbergii - Kun Xie; Yu-Meng Shi; Jin-Xia Yang; Jia-Yan Chen; Xu Huang; Xin-Yu Liu; Li-Ping Chen; Jie Chen; Chao-Ping Lu; Gao-Feng Qiu (Marine Biotechnology, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

Undescribed dihydro- β -agarofuran sesquiterpenoids from the roots of Tripterygium wilfordii - Ya-Lin Hu; Jia-Li Huang; Chong Wang; Wen-Jie Chen; Jing-Yi Huang; Yi-Ping Xie (Natural Product Research, 2026)

Chemical constituents from Helvella leucopus and their chemotaxonomic significance - Zhao-Zhao Zhang; Yi-Yang Xie; Li-Ping Teng; Zhong-Bo Zhou (Biochemical Systematics and Ecology, 2026)

Lowering cyclosporine trough concentration threshold effectively mitigates acute graft-versus-host disease in children with severe β-Thalassemia post hematopoietic stem cell transplantation - Zhuolin Yang; Xianggui Wang; Xiaojing Wang; Wenjiao Ding; Yiyu Zhang; Qingling Gu; Wenqing Wang; Yousi Miao; Ping Xie; Min Huang; Hua Jiang; Xiaolan Mo; et al. (European Journal of Clinical Pharmacology, 2026)

Toonamonoids A and B: two new limonoids from Toona ciliata var . yunnanensis (C.DC.) C.Y.Wu and their cytotoxic activity - Mingwang Luo; Shengyun Wei; Weihua Wang; Wei Yang; Lu Li; Yujie Li; Qiangxin Zhang; Sida Xie; Xiaoqin Yang; Ping Zhao; Guolei Zhu (Natural Product Research, 2025)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Coupled biogeochemical processes account for vertical heterogeneity of groundwater iodine in the Hetao Basin - Junxia Li; Xingtao Liu; Zhou Jiang; Liang Shi; Yanhong Wang; Ping Li; Xianjun Xie; Yanxin Wang (Water Research, 2025)

Identifying conservation gaps and proposing climate-smart strategies for amphibians and reptiles on the Qinghai-Tibet Plateau - Lu-Lu Sui; Zhong-Yi Yao; Shun Ma; Sheng-Chao Shi; Xiu-Dong Shi; Li-Wen Liang; Song Tan; Jie Wang; Bo Cai; Feng Xie; Jing-Feng Chen; Bin Wang; et al. (Journal of Environmental Management, 2025)

The variation of the East Asian summer monsoon on multi-centennial scale during 8.3–2.9 ka BP - Chao-Jun Chen; Ya-Xi Dong; Yao Wu; Jian Zhang; Hai-Bo Wang; Yan-Xia Xue; Wen-Jun Sun; Man-Ping Xie; Hai Cheng; Jun-Yun Li; Ming-Qiang Liang; Ting-Yong Li (Global and Planetary Change, 2025)

The probiotic characteristics and antimicrobial mechanisms of Lactiplantibacillus plantarum ZFM55 - Shiying Wu; Jiayi Fan; Yi Xu; Yuenuo Luo; Luying Xie; Mingyang Hu; Yongqiang Chen; Fangtong Wei; Yuqing Lou; Ping Li; Qing Gu (Food Bioscience, 2025)

Natural compound rhein-based bimetallic nanosheets to induce ferroptosis and activate STING pathway for enhanced cancer immunotherapy - Chang Li; Tiancheng Xie; Xilong Mei; Yu Wen; Mi Huang; Hu Guo; Ping Lu; Xiaoxin Yang; Jun Liu (Chemical Engineering Journal, 2025)

MOF-derived porous Co Mn bimetallic oxide for efficient peroxymonosulfate activation: Electron transfer pathway transition steered by synergistic effect of nanoconfinement and bimetallic sites - Xun Xu; Xiaojie Ji; Yuankang Bao; Luliang Liao; Ping Li; Hao Zhang; Yaqiang Xie; Shuwang Duo (Chemical Engineering Journal, 2025)

High-intensity fish disturbance reduces ecosystem multifunctionality by diminishing planktonic bacterial diversity and network complexity - Shangsheng Sun; Jianfeng Chen; Qingyang Rao; Yuwei Wang; Ruyi Li; Misha Zhong; Yihan Wang; Zengliang Jian; Chaokun Wang; Yafang Qin; Yulian Chu; Ping Xie; et al. (Biological Conservation, 2025)

Comparative chloroplast genomic analysis: uncovering variations and phylogenetic relationships in tea plants from Shaoyang, Hunan Province, China - Jin Li; Yu Qin; Jun Tang; Xiao-Yan Qiu; Chang-Qing Xie; Han Tang; Ai-Ming Tang; Xiao Chen; Jun-Ping Xie; Hua Luo (Genetic Resources and Crop Evolution, 2025)

CPT1A facilitated ferroptosis by forming feedback loop with Nrf2 via PI3K/AKT pathway in colorectal cancer - Xiao-huan Li; Feng Lv; Si-qi Li; Hao-wei Deng; Li-ping Tang; Ke-zhi Li; Li-ye Xie; Bang-li Hu; Shu-fang Ning (Apoptosis, 2025)

Beyond biodiversity: The more essential role of multi-trophic network complexity for predicting ecosystem multifunctionality under multiple stressors - Shangsheng Sun; Haojie Su; Qingyang Rao; Jianfeng Chen; Yafang Qin; Yongchao Peng; Chaoyue Cheng; Misha Zhong; Ruijing Ma; Yuwei Wang; Yihan Wang; Zengliang Jian; et al. (Water Research, 2025)

Multiscale responses of gap-graded soil under the combined effect of train vibration and seepage erosion - Dong-Mei Zhang; Hui-Hao Chen; Xiao-Chuang Xie; Si-Rui Chen; Zhao-Geng Chen; Jia-Ping Li (Transportation Geotechnics, 2025)

Sorafenib induces intestinal toxicity by disturbing gut microbiota and activating the LPS/TLR4/NF-κB signaling pathway in mice - Yaning Xu; Yongshi Mo; Wenxin Zhou; Meirong Qin; Meifang Li; Guo Yin; Hansheng Yu; Yuchun Chen; Haiyan Du; Yibao Jin; Houshuang Huang; Chong Ma; et al. (Toxicology, 2025)

miR-927 links nutrient signals and 20-hydroxyecdysone regulation and mediates oviposition in Bactrocera dorsalis - Tong-Jun Jin; Zheng-Yang Wang; Qian-Ping Xie; Li-Yuan Zheng; Guy Smagghe; Jin-Jun Wang; Qiang Zhang; Wei Dou (Insect Biochemistry and Molecular Biology, 2025)

[3 + 2 + 1] iridium(III) complexes for high-efficiency saturated red organic light-emitting diodes - Ping Chen; Qingwu Wu; Gui-Yan Yang; Qifei Xie; Sheng Yu; Ming-Yu Teng; Huabo Han; Guo-Li Huang; You-Xuan Zheng; Guangzhao Lu (Chemical Engineering Journal, 2025)

The dietary supplementation with probiotic Bacillus cereus G1-11 improved the growth parameters, immune performances, intestinal histomorphology, and disease resistance of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Ming-Qing Zhang; Zhong-Xuan Zhong; Qian-Ping Du; Wen Li; Ya-Ting Zhu; Guang-Ting Xie; Feng-Ying Yan; Jin-Lin Yang; Shui-Sheng Li; Hu Shu (Animal Feed Science and Technology, 2025)

Bioaugmentation with novel heterotrophic nitrifying bacteria enhances nitrogen removal in low C/N wastewater: Elucidating nitrogen metabolic traits and reactor-scale validation - Yuji Dong; Tianyi Zhang; Liuan Xie; Jiapeng Ping; Lihong Zhang; Yuxuan Huang; Huiting Song; Chuan Li (Journal of Environmental Chemical Engineering, 2025)

Targeted gene therapy for intracranial aneurysm using SOX17-CRISPRa - Dujie Xie; Yi Yuan; Panyao Long; Juan Huang; Mi Jiang; Yongzhong Tang; Yuanqiang Luo; Cancan Zhang; Ping Zheng; Liang Yang; Yiwei Chen; Xiaobo Li; et al. (Chemical Engineering Journal, 2025)

VUV photoelectron ionization source for molecular beam mass spectrometer and its application for SF6 discharge product detection - Peng Liu; Chenxin Wu; Shan Deng; Yuanyuan Xie; Lei Hua; Haiyang Li; Shengrui Yu; Ping Chen (Analytica Chimica Acta, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Changes in cell wall characteristics and expression of MiERF12, MiERF109-like, and MiERF113 during mango softening - Yuhan Long; Lihong Xie; Ping Yi; Fang Huang; Min Huang; Ting Gan; Jian Sun; Li Li; Hao Dong; Qi Wei; Zhenmei Fan; Qiuyu Cheng (Postharvest Biology and Technology, 2025)

Tracing mercury sources and transfer pathways in Pacific and Atlantic Ocean tuna and billfish using mercury stable isotopes - Ruo Lan; Feng Wu; Jingqian Xie; Shaochen Yang; Xingyu Liang; Zhiyang You; Ping Li; Runsheng Yin; Xinbin Feng (Journal of Hazardous Materials, 2025)

Effect of blanching times and drying temperatures on the color, moisture migrations, microstructures, phytochemicals, and flavors of chili pepper (Capsicum annuum L.) - Yongkang Xie; Junjun Geng; Ping Li; Yan Zhao; Junhao Han; Hui Yang; Shina Cao (Food Chemistry, 2025)

Osthole inhibits proliferation and induces autophagy-dependent ferroptosis of cervical cancer cells through induction of TFR1 - Linjun Li; Yue Zhao; Xiaojuan Li; Muzhao Tian; JiaoQing Wei; Wanyu Xie; Caishan Liu; Ping Dai; Juan Wang (Food and Chemical Toxicology, 2025)

Polyethylene biodegradation by gut microbiota of Lasioderma serricorne: Isolation, identification, and mechanistic insights - Ming-Fei Wu; Pan-Pan Jia; Ling He; Li-Ping Ma; Yan Li; Lan-Chen Zhang; Dong-Mei Xie; Xiao-Bing Li; Tian-Nv Wang; De-Sheng Pei (Chemical Engineering Journal, 2025)

Graphene quantum dots induce hexagonal CdS prism formation and interparticle Z-scheme heterojunctions for efficient Hg0 removal under visible light - Xi Zhou; Yibing Xie; Lu Wang; Langlang Wang; Xiang Li; Ping Ning; Xueqian Wang (Chemical Engineering Journal, 2025)

Visualization of MC-LR in lakes using near-infrared technology - Huiyan Chuan; Bingyan Li; Zhaomin Wang; Yue Zhang; Ping Xie; Yong Liu (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

BarleyOmics: A comprehensive multi-omics database of barley - Junheng Zhao; Shanggeng Xie; Chenyang Zhang; Zengjie Hu; Xiangqian Lu; Nannan Zheng; Yujie Fu; Jie Yao; Ping Zhou; Danyin Huang; Zhizhong Zhang; Mengdi Li; et al. (Molecular Plant, 2025)

Environment-specific fluorescence probe for investigating the detection mechanism of nitric oxide in lakes - Zhe Chen; Ronghua Li; Syed Turab Raza; Eldon R. Rene; Ping Xie; Yong Liu (Journal of Hazardous Materials, 2025)

Tracing anthropogenic imprints on polybrominated and polychlorinated dibenzo-p-dioxin/furans in soil: A comprehensive field study in an urban agglomeration of China - Ming-Yang Liu; Hui-Ru Li; Ping-An Peng; Ai-Min Song; Yang Li; Fei-Xiang Xie; Yong-Hong Zhang; Jian-Fang Hu (Environmental Research, 2025)

Investigating fracture response characteristics and fractal evolution laws of pre-holed hard rock using infrared radiation: Implications for construction of underground works - Ze-Kun Zhang; Jin-Xing Lai; Zhan-ping Song; Yong-Li Xie; Jun-ling Qiu; Yun Cheng; Le Zhang (Tunnelling and Underground Space Technology, 2025)

Advances and challenges of medicine and food homology earthworms: active ingredients, efficacy and quality control - Siqi Lu; Xiaoqin Xie; Tao Xu; Junqi Dong; Shengrong Li; Zenghui Lu; Ping Shi; Pixian Gong; Wei Liu (Trends in Food Science & Technology, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

Selective and controllable mechanism of the temperature field in skin tissue under radiofrequency heating: finite element analysis and ex-vivo pig skin experiments - Ping Zhu; Chuanqi Xie; Kai Li; Fangjie Shu; Liqiang Li; Zhaodi Su; Yue Xue (Journal of Thermal Biology, 2025)

Study of the bubble flow evolution and load characteristics of a three-dimensional trimaran model entering water - Yanna Ping; Shuo Li; Fang Liu; Hang Xie (Ocean Engineering, 2025)

Characterization and functional analysis of the small heat shock protein HSP19.5 in Bombyx mori in response to Nosema bombycis infection - Zhenghao Han; Shidong Jiang; Jingxian Xie; Ibouanga Sama Lucreche Poupina; Xiaoli Mo; Li Sui; Ping Qian; Xudong Tang (Journal of Invertebrate Pathology, 2025)

In vitro and in vivo antibacterial effects of indole-3-lactic acid against Salmonella enterica serovar Typhimurium - Qingqing Zhou; Yajun Yu; Zuorui Xie; Yingying Zhou; Yanan Li; Ping Li; Jiangning Hu; Qing Gu (Food Bioscience, 2025)

Altering wilting time and chopping length to optimize Medicago polymorpha L. fermentation ripening rate and flavour - Ning Mao; Hanyu Zhang; Ermei Du; Meiling Fan; Shihao Liu; Chaosheng Liao; Chao Chen; Hong Sun; Yulong Zheng; Ping Li; Yixiao Xie (Food Bioscience, 2025)

Terpene-conjugated curcumin analogs alleviated alcoholic liver injury in rats through mitigation of intestinal barrier abnormalities - Shuaihu Tao; Ruanping Song; Ziyu Wang; Wenjing Xie; Siyuan Xiao; Yangyang Liao; Xinjie Zhang; Qiongdan Hu; Xinxing Tang; Jingyuan Huang; Wan Liao; Hongtao Xiao; et al. (Food Bioscience, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Warming Enhances the Effects of Acidification on Aquatic Biota: A Global Meta‐Analysis - Zengliang Jian; Misha Zhong; Ruyi Li; Haojie Su; Qingyang Rao; Yihan Wang; Chaokun Wang; Shangsheng Sun; Jianfeng Chen; Ping Xie (Global Ecology and Biogeography, 2025)
Aim Global elevated atmosphere CO 2 concentration‐induced acidification poses a great threat to aquatic organisms worldwide. However, a comprehensive understanding of the response variability to acidification is still lacking, especially in the context of concurrent global warming. Addressing the response patterns of aquatic biota to acidification under the context of warming can facilitate the identification and prediction of probable consequences of global climate change. Location Global. Time Period 1996–2024. Major Taxa Studied Aquatic biota. Methods We performed a meta‐analysis by synthesising 221 studies containing 3669 observations to summarise the effects of CO 2 on multiple aquatic biota, including primary producers, consumers, and decomposers. We further examined the effects of different ecosystems, experimental venue, CO 2 concentration, and ambient experimental temperature on the response magnitude. Results Acidification had significant positive effect on primary producers and decomposers, yet significant negative effect on consumers. We found that invertebrates were the most negatively affected of all organisms, and the marine ecosystems are suffering more severity of acidification than freshwater ecosystems. We further found that the response magnitude showed a significant dose effect, indicating that reducing greenhouse gas emissions would minimise the impact of acidification. In addition, we found that higher temperatures enhanced the sensitivity of primary producers to acidification, suggesting that global climate warming may interact with acidification in a synergistic way. Main Conclusions Our results showed that distinct trophic levels showed significant differences in the response direction and magnitude. Specifically, the consumer is generally the most sensitive trophic level that is negatively affected by acidification. We emphasise that the simultaneous exposure of primary producers to anthropogenic stressors associated with acidification and warming is expected to produce interactions that may potentially reinforce the negative consequences, which is key to predicting and mitigating the acidification effect under future climate change scenarios.

FDEM numerical study on the large deformation mechanism of layered rock mass tunnel under excavation-unloading disturbance - Ping Liu; Hongtao Wang; Quansheng Liu; Xiaojing Li; Yuanxuan Dong; Xianqi Xie (Tunnelling and Underground Space Technology, 2025)

Enhanced activation of peroxymonosulfate by nickel sulfide with sulfur vacancies for ultrafast organic pollutants degradation: Roles of active sites and mechanism - Cai-Wu Luo; Liang Jiang; Xian-Feng Li; Qiang-Mao Wan; Tian-Jiao Jiang; Sen-Ping Mao; Jing-Qian Guo; Run-Ze Zhao; Chao Xie (Environmental Pollution, 2025)

Gradient-Structured sodiophilic skeleton integrated with spatial confinement effect Enables high-rate and ultra-stable Na metal batteries - Fang-Yu Tao; Dan Xie; Wan-Yue Diao; Chang Liu; Godefroid Gahungu; Wen-Liang Li; Jing-Ping Zhang (Chemical Engineering Journal, 2025)

Raman spectroscopy coupled with chemometrics for identification of adulteration and fraud in muscle foods: a review - Haiyang Ma; Jiajun Guo; Guishan Liu; Delang Xie; Bingbing Zhang; Xiaojun Li; Qian Zhang; Qingqing Cao; Xiaoxue Li; Fang Ma; Yang Li; Guoling Wan; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Minor protopanaxadiol type sapogenins from the alkali hydrolysate of stems-leaves of Panax notoginseng - Cong-Cong Jing; Jing-Min Wang; Pei Wang; Lin Guo; Shu-Min Zhang; Ke Liu; Zhen-Yuan Li; Hua-Ying Fan; Ze-Ping Xie (Natural Product Research, 2025)

Dynamic analysis of fungal community and metabolome associated with postharvest diseases in banana peel under natural condition - Ping Yi; Ming Zhao; Fang Huang; Li Li; Jian Sun; Lihong Xie; Dongning Ling; Jiemin Li; Min Huang; Ting Gan; Yayuan Tang; Changbao Li; et al. (Postharvest Biology and Technology, 2025)

Screening, identification, and mechanism of novel antioxidant peptides in walnut meal under aerobic stress - Hui Ouyang; Xiaolong Liu; Jiaying Huo; Ping Wang; Tingting Xie; Xiongwei Yu; Shugang Li; Ying Gao (Food Chemistry, 2025)

Advancing lactic acid Fermentation: Effects of micro aeration and herbal waste on red clover bioconversion - Chaosheng Liao; Mingjie Zhang; Pan Wang; Xiaolong Tang; Minghong You; Changbing Zhang; Guofu Jia; Wenlong Gou; Ning Mao; Yixiao Xie; Chao Chen; Shiqie Bai; et al. (Chemical Engineering Journal, 2025)

Metabolic mechanism, responses, and functions of genes HDH1, HDH3, and GST1 of tea (Camellia sinensis L.) to the insecticide thiamethoxam - Ping Zhang; Tianyuan Yang; Yunlong Xie; Yulong Liu; Qing X. Li; Xiangwei Wu; Rimao Hua; Weiting Jiao (Journal of Hazardous Materials, 2025)

Impact of eight extruded starchy whole grains on glycemic regulation and fecal microbiota modulation - Fang Fang; Yu-Xin He; Hao-Qiang Wang; Yan-Li Zhang; Ya-dong Zhong; Xiao-Tian Hu; Shao-Ping Nie; Ming-Yong Xie; Jie-Lun Hu (Food Hydrocolloids, 2025)

Growth, biochemical indexes, and intestinal microbiota response of red tilapia (Oreochromis spp.) under different densities and feeding frequencies in the land-based aquaculture tank - Yu-Xiang Xie; Jun-Neng Liang; Gen Kaneko; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Qiong Yang; Zhen-Ping Liao; Xue-Ming Yang; Hong-ping Zhang; Lin-Yuan Jiang; et al. (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Metabolomics-based mechanistic insights into antioxidant enhancement in mango juice fermented by various lactic acid bacteria - Shuai Liu; Yu-Jia Peng; Wei-Wei He; Xiao-Xiao Song; Yu-Xin He; Xiao-Yi Hu; Shui-Gen Bian; Yu-Hao Li; Jun-Yi Yin; Shao-Ping Nie; Ming-Yong Xie (Food Chemistry, 2025)

Astragalus polysaccharide/carboxymethyl chitosan/sodium alginate based electroconductive hydrogels for diabetic wound healing and muscle function assessment - Letian Tang; Shuyang Xie; Danyang Wang; Yiying Wei; Xiaopu Ji; Yicheng Wang; Nana Zhao; Zonglei Mou; Baoping Li; Wan Ru Sun; Ping Yu Wang; Nicola Paccione Basmadji; et al. (Carbohydrate Polymers, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Identification and characterization of GRAS genes in passion fruit (Passiflora edulis Sims) revealed their roles in development regulation and stress response - Xinkai Cai; Denglin Li; Chaojia Liu; Jiayi Chen; Xiuqing Wei; Sitong Hu; Lin Lu; Shengzhen Chen; Qinglong Yao; Shiyu Xie; Xiaowen Xu; Ruoyu Liu; et al. (Plant Cell Reports, 2025)

Key process of ethanol hydrogen donor promoting the conversion of organic matter in sludge to bio-oil - Quxiu Dai; Linglong Zeng; Qihong Cen; Wang Du; Ping Ning; Kai Li; Zhiying Guo; Ran Ao; Longgui Xie; Nanqi Ren; Liping Ma; Jie Yang; et al. (Water Research, 2025)

Strategic PNDI(2OD)2T doping for all-perovskite tandem solar cells with enhanced efficiency and durability - Ziang Xie; Shiping Zhang; Sen Chen; Yili Pei; Li Li; Jinguang Yang; Guodong Fu; Ping Wu (Chemical Engineering Journal, 2025)

In-situ fabrication of TiO2/ZIF-67 composite film with electron storage characteristics for significantly enhanced photoelectrochemical cathodic protection of 304 stainless steel - Shouwu Xu; Zhilong Zhang; Hailin Zhang; Zhiwei Li; Haoping Peng; Sibudjing Kawi; Aijun Xie; Ping Qiu (Chemical Engineering Journal, 2025)

Varied chromosome distribution behaviours during meiosis in triploid Chinese chives contribute to the formation of viable pollen - Peng-Qiang Yao; Li-Hua Xie; Mei-Yu Li; Si-Qian Jiao; Shuai-Zheng Qi; Zhe Wang; Shi-Ping Cheng (Chromosome Research, 2024)

Miocene evolution of vegetation, climate, and elevation in the Wulan Basin of northeast Tibetan Plateau based on a CRACLE analysis of palynological assemblages - Xiao-Mei Li; Jia-Yi Chen; Zhen-Dong Cao; Li-Ming Liu; Si-Hang Zhang; Yun-Zhe Zhang; Li-Jie Wei; San-Ping Xie (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Closed-loop recycling of biodegradable poly(butylene adipate-co-terephthalate) based on hydrolysis and repolymerization strategy - Wei-Zhen Zheng; Xiao Li; Jing Xie; Ze-Yang Zhang; Ping-Li Wang; Dan Huang; Zhong-Lai Ren; Jun-Hui Ji; Ge-Xia Wang (Journal of Environmental Chemical Engineering, 2024)

Tectonic-climate-wildfire coupling during the Miocene in the northeastern Qinghai-Tibetan Plateau - Li-Ming Liu; Zhen-Dong Cao; Xiao-Mei Li; Si-Hang Zhang; Yun-Zhe Zhang; Jia-Yi Chen; De-Fei Yan; San-Ping Xie (Journal of Asian Earth Sciences, 2024)

Chemical characteristics, sources, and formation mechanisms of PM2.5 before, during, and after the Spring Festival in a plateau city of Southwest China - Jianwu Shi; Li Deng; Wei Du; Xinyu Han; Yaoqian Zhong; Wenjun Rao; Haitao Xie; Feng Xiang; Ping Ning; Senlin Tian (Atmospheric Environment, 2024)

Streptomyces cathayae sp. nov., an endophytic actinobacterium from the root tissue of Cathaya argyrophylla - Ping Mo; Can Wu; Ruonan Han; Zhongyuan Chen; Yushuang Luo; Peng Xie; Li Li; Yun Wang (Antonie van Leeuwenhoek, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Evolution and legacy of East Asian aurochs - Jiawen Hou; Xiwen Guan; Xiaoting Xia; Yang Lyu; Xin Liu; Yuri Mazei; Ping Xie; Fengqin Chang; Xiaonan Zhang; Jialei Chen; Xinyi Li; Fengwei Zhang; et al. (Science Bulletin, 2024)

Modeling the impact of long-term land use changes on deep soil hydrological processes in the Loess Plateau, China - Yakun Wang; Yanan Jiang; Ying Zhao; Xinbo Li; Kun Xie; Ting Yan; Tingting Wei; Ping Li; Huijie Li (Journal of Hydrology, 2024)

Study of Cerchar abrasive parameters of monomineralic rocks and its application for evaluating cutting efficiency - Xin-Fang Li; Xiao-Ping Zhang; Shao-Hui Tang; Wei-Qiang Xie; Xin-Mei Yang; Quan-Sheng Liu (International Journal of Rock Mechanics and Mining Sciences, 2024)

Acid-assisted pretreatment for sweet elephant grass in choline chloride/glycerol DES: Experimental and mechanism study - Yining Zhang; Weizhen Xie; Weidong Li; Yue Tang; Jiali Wu; Lihui Gan; Ling-Ping Xiao; Xu Zhang; Lu Lin; Xing Tang (Chemical Engineering Journal, 2024)

The effect of pegmatite veins on fracture behaviors of granite in a deep large underground cavern - Yuelin Xia; Ding-Ping Xu; Quan Jiang; Jianbin Xie; Zhiguo Li (Bulletin of Engineering Geology and the Environment, 2024)

Otolith Microchemistry Reveals the Diversity of Migration Patterns and Spawning Ground Distribution of Coilia nasus from the Yangtze River Estuary - Chao Song; Wenjie Yu; Ruohui Liu; Jilin Xie; Feipeng Li; Feng Zhao; Ping Zhuang (Fishes, 2024)
Coilia nasus are an important fish resource in the Yangtze River, and the Yangtze River Estuary is a crucial migration pathway for them. In this study, we used otolith microchemistry to analyze the strontium/calcium (Sr/Ca) ratios and Sr contents in the sagitta otolith of C. nasus from the south branch (SB) and north branch (NB) of the Yangtze River Estuary and obtained the diversity of migration patterns and spawning ground distribution for C. nasus. The results indicate that C. nasus from both branches include two types of habitat history: freshwater (F)–brackish water (B) (Type I) and F-B seawater (S) (Type II), with Type I being dominant at 62.50% in both branches. The C. nasus from the SB comprise six migration patterns, while that from the NB has seven migration patterns. The C. nasus from both branches hatch in F habitats. At the time of capture, the C. nasus from the SB predominantly remain in F, accounting for 62.5%, while C. nasus from the NB primarily stay in B, accounting for 87.5%. Throughout the migration process, C. nasus from both branches switch between different habitats, with C. nasus from the NB exhibiting more frequent transitions between F and B, showing a greater reliance on the estuarine brackish habitat. The radius of the first blue region near the core (Lf) and freshwater coefficient (Fc) of the otolith for C. nasus from both branches are divided into three groups: long-distance freshwater dependence (LD), medium-distance freshwater dependence (MD), and short-distance freshwater dependence (SD), with the LD only appearing in the SB, while the NB is primarily represented by MD. There is a correlation between the differences in Lf among different groups of C. nasus and the differences in the distance from the spawning grounds of C. nasus in different sections of the Yangtze River to the estuary (DYRE), reflecting the distribution pattern of C. nasus spawning grounds in different sections of the Yangtze River. This study provides theoretical guidance for the protection of migration pathways and maintenance of spawning grounds for C. nasus, which have significant practical value in the precise management of C. nasus resources in the Yangtze River Estuary.

Crystal phase conversion of amorphous Fe−Mn binary oxides promote the sequestration and redistribution of arsenic, cadmium, and lead in the soil: Comparison with crystalline form - Junhao Zheng; Yan Xie; Yang Ping; Hao Xu; Qi Li; Qi Liao; Qingzhu Li; Zhihui Yang; Weichun Yang; Mengying Si (Journal of Environmental Chemical Engineering, 2024)

Exploring the lipid oxidation mechanisms during pumpkin seed kernels storage based on lipidomics: From phenomena, substances, and metabolic mechanisms - Li Pan; Weijian Xu; Ying Gao; Hui Ouyang; Xiaolong Liu; Ping Wang; Xiongwei Yu; Tingting Xie; Shugang Li (Food Chemistry, 2024)

Segmentation of wood CT images for internal defects detection based on CNN: A comparative study - Guangqiang Xie; Lihai Wang; Roger A. Williams; Yaoxiang Li; Ping Zhang; Sheng Gu (Computers and Electronics in Agriculture, 2024)

A citrullinated antigenic vaccine in treatment of autoimmune arthritis - Xu Jin; Tianya Dong; Qian Wang; Yang Xie; Xiangyu Fang; Chaonan Wei; Shuyan Liu; Xi Zheng; Ping Wang; Danxue Zhu; Lulu Cao; Suwei Dong; et al. (Science Bulletin, 2024)

The impact of dissipative algorithms on assessment of high-speed train running safety on railway bridges - Han Zhao; Biao Wei; Zhanjun Shao; Xiaonan Xie; Peng Zhang; Huifang Hu; Yingying Zeng; Lizhong Jiang; Changqing Li; Ping Xiang (Engineering Structures, 2024)

Fe-reinforced silkworm silk with superstrong mechanical properties for mass production - Qingsong Liu; Xin Wang; Yifan Zhou; Yi Li; Zhangchuan Peng; Zhangchen Tang; Xiangyu Cai; Xinyu Fan; Xin Tang; Xiaoyin Tan; Xiaoqian Xie; Xinning Li; et al. (Chemical Engineering Journal, 2024)

Rapid and sensitive detection of SARS-CoV-2 based on a phage-displayed scFv antibody fusion with alkaline phosphatase and NanoLuc luciferase - Yuxue Yan; Guofu Shang; Jiling Xie; Yingying Li; Shaomei Chen; Yanqin Yu; Ping Yue; Xiaoyan Peng; Min Ai; Zuquan Hu (Analytica Chimica Acta, 2024)

Inventorization and ecological risk assessment of tetrabromobisphenol A and hexabromocyclododecane in sediments from Guangdong coastal area of South China Sea - Xiaoxia Chen; Xin Li; Yuqing Fan; Guocheng Hu; Hang Xie; Xiaoyan Chen; Ping Ding; Yao Dang; Xiyuan Hu; Qinghua Chen (Science of The Total Environment, 2024)

Histology and transcriptomic analysis reveal the inflammation and affected pathways under 2-methylisoborneol (2-MIB) exposure on grass carp - Huan Han; Jun-ming Zhang; Shuang Ji; Xiang-biao Zeng; Xi-chen Jin; Zi-qian Shen; Bin Xie; Xue-neng Luo; Kang Li; Li-ping Liu (Science of The Total Environment, 2024)

Modulating proportion of Ni0 species stabilized by Ni2+ on Ni-MgO catalyst with superior stability for dry reforming of methane - Xieyi Liu; Junjie Wen; Yu xie; Zongling Li; Manshu Zhong; Rongbing Nie; Shiyuan Peng; Jinyan Cao; Jianjun Chen; Ping Ning; Qiulin Zhang (Chemical Engineering Journal, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

An engineered DNA aptamer-based PROTAC for precise therapy of p53-R175H hotspot mutant-driven cancer - Lingping Kong; Fanlu Meng; Ping Zhou; Ruixin Ge; Xiaoshan Geng; Zhihao Yang; Guo Li; Linlin Zhang; Jing Wang; Jinfeng Ma; Cheng Dong; Jun Zhou; et al. (Science Bulletin, 2024)

Effects of four antibiotics on the photosynthetic light reactions in the green alga Chlorella pyrenoidosa - Feifan Wang; Ping Liu; Jiajun Li; Siting Xu; Hongxing Chen; Lingtian Xie (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Gypenoside XLIX alleviates intestinal injury by inhibiting sepsis-induced inflammation, oxidative stress, apoptosis, and autophagy - Kaixin Ping; Rongrong Yang; Huizhen Chen; Shaocheng Xie; Mengxin Li; Yannan Xiang; Yingzhi Lu; Jingquan Dong (Chemico-Biological Interactions, 2024)

Analysis of Root Response Mechanism of Quinoa Seedlings to Waterlogging Stress Based on Metabolome - Yirui Guo; Qianchao Wang; Heng Xie; Xuesong Zhang; Tingzhi Huang; Ping Zhang; Junna Liu; Li Li; Peng Qin (Journal of Plant Growth Regulation, 2024)

Sulfur doping-induced morphological and electronic structure modification of polyoxometalate FeWO4 for enhanced removal of organic pollutants from water - Dong-Hua Xie; Wen-Qiang Li; Nuo Xu; Li Yuan; Wen-Hua Zhang; Tian-Yin Huang; Guo-Ping Sheng (Water Research, 2024)

The origins of odor (β-cyclocitral) under different water nutrient conditions: Algae or submerged plants? - Yu Lin; Chaoyue Cheng; Yutai Dai; Weijie Li; Jiping Chen; Mo Chen; Ping Xie; Qiang Gao; Xiaoyue Fan; Xuwei Deng (Science of The Total Environment, 2024)

Human health risk assessment and toxic effect of heavy metal(loid)s in Bamboo shoot products - Yu-Mei Xie; Meng-Yan Zhang; Fei-Peng Liu; Cheng-Chen Wang; Wen-Yuan Dong; Chun-Mei Xu; Xin Li; Wu-Mei Xu; Ping Xiang (Journal of Environmental Chemical Engineering, 2024)

Chemical constitutents and chemotaxonomic research of the deep-sea-derived fungus Talaromyces minioluteus W19 - Kai Zhang; Yuan Wang; Teng Long; Ya-Ping Xie; Zheng-Biao Zou; Yong Zhang; You Li; Ming-Min Xie; Guang-Ming Liu; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Karyotype analysis of Chinese chive germplasms with different ploidy levels and their evolutionary relationships - Peng-Qiang Yao; Jian-Hua Chen; Pei-Fang Ma; Li-Hua Xie; Jiang Shi; Shi-Ping Cheng (Genetic Resources and Crop Evolution, 2024)

Geochemical characteristics of Ordovician crude oils in the FI17 strike-slip fault zone of the Fuman oilfield, Tarim basin: Implications for ultra-deep hydrocarbon accumulation in the Tarim basin - Zhongdeng Lu; Hongwei Ping; Honghan Chen; Yanqiu Zhang; Zhou Xie; Yintao Zhang; Zulin Chen; Xin Yang; Xinle Zhang; Kang Yang; Xiaoqiang Li (Marine and Petroleum Geology, 2024)

A water quality assessment model involving novel fluorescence technology - Yu Hao; Yue Zhang; Bingyan Li; Huiyan Chuan; Zhaomin Wang; Jianping Shen; Zhe Chen; Ping Xie; Yong Liu (Journal of Environmental Management, 2024)

Correlation of Immune-Inflammatory Response System (IRS)/Compensatory Immune-Regulatory Reflex System (CIRS) with White Matter Integrity in First-Episode Patients with Schizophrenia - Mengzhuang Gou; Wei Li; Jinghui Tong; Yanfang Zhou; Ting Xie; Ting Yu; Wei Feng; Yanli Li; Song Chen; Baopeng Tian; Shuping Tan; Zhiren Wang; et al. (Molecular Neurobiology, 2024)

Experimental study on the influence mechanism of soil additives on scraper wear during EPB-TBM tunnelling in abrasive sandy ground - Shao-Hui Tang; Xiao-Ping Zhang; Quan-Sheng Liu; Wei-Qiang Xie; Jian Wu; Hao-Jie Wang; Xin-Fang Li (Bulletin of Engineering Geology and the Environment, 2024)

Gamma-ray irradiation as an effective method for mitigating antibiotic resistant bacteria and antibiotic resistance genes in aquatic environments - Ming-Qi Zhang; Xiao-Yong Zhang; Han-Chao Zhang; Hai-Bin Qiu; Zheng-Hao Li; Dong-Hua Xie; Li Yuan; Guo-Ping Sheng (Journal of Hazardous Materials, 2024)

The removal mechanisms of HF and HCl gases using Mg-Al adsorbent prepared by sol-gel synthesis method - Peng Gao; Jiayu Feng; Yuxuan Xie; Xinyu Yang; Ping Ning; Xin Sun; Fei Wang; Lei Shi; Jie Zhao; Kai Li (Journal of Environmental Chemical Engineering, 2024)

Insights into the differences in metal anchoring mechanisms and the impact on HCN catalytic oxidation performance - Zhao Li; Jiawen Tan; Yuxuan Xie; Xinyu Yang; Chunxue Wang; Kai Li; Ping Ning; Fei Wang (Fuel, 2024)

Exploration of markers in oxidized rancidity walnut kernels based on lipidomics and volatolomics - Jiaying Huo; Wu Peng; Hui Ouyang; Xiaolong Liu; Ping Wang; Xiongwei Yu; Tingting Xie; Shugang Li (Food Research International, 2024)

Association between exposure to outdoor artificial light at night during pregnancy and glucose homeostasis: A prospective cohort study - Lei Zhang; Haixia Wang; Ping Zu; Xinyu Li; Shuangshuang Ma; Yuanyuan Zhu; Tianqin Xie; Fangbiao Tao; Dao-min Zhu; Peng Zhu (Environmental Research, 2024)

Seasonal variations and size-dependent distribution of heavy metals in particulate matter in Huangshi: Implications for human health risk assessment - Yuhu Xie; Yao Mao; Ping Zhong; Yong Zhang; Li Zhang; Wei Chen; Chengkai Qu; Xinli Xing; Junji Cao; Jiaquan Zhang (Atmospheric Environment, 2024)

An untargeted metabolomics analysis of the components of heartwood and sapwood in 4 fast-growing Chinese fir (Cunninghamia lanceolata (Lamb.) Hook) clones - Xiaoqin Yang; Liping Li; Xiaorui Yu; Yun Liu; Sida Xie; Guolei Zhu; Junming Xu; Ping Zhao (Trees, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

The relationships between vertical variations of shallow gas and pore water geochemical characteristics in boreholes from the inner shelf of the East China Sea - Xue Li; Xiaoyong Duan; Xingliang He; Yongqing Xie; Lei Yang; Ping Yin; Ke Cao; Bin Chen; Fei Gao; Feng Li (Frontiers in Marine Science, 2024)
Shallow gas was widely recognized in the coastal region, especially in the estuarine delta areas with high organic matter (OM) burial flux. In this study, the vertical variations of shallow gas and the related geochemical indicators from two boreholes in the coastal region of the East China Sea (ECS) were investigated. Two gas-bearing layers were identified in the sediments from the Holocene and late Pleistocene series. Both boreholes exhibit a “typical” and an “inverse” Sulfate Methane Transition Zone (SMTZ). The “typical” SMTZs (SMTZ1 and SMTZ3) were in the upper part of the gas-bearing layers, where sulfate levels decrease and methane levels increase with depth. Conversely, the “inverse” SMTZs (SMTZ2 and SMTZ4) were in the lower part of the gas-bearing layers, exhibiting an increase in sulfate levels and a decrease in methane levels with depth, a phenomenon rarely documented in previous research. The downward variations of pore water geochemical characteristics indicates that these ions were related to Anaerobic Oxidation of Methane (AOM) processes. The increase in Ca 2+ and Ba 2+ concentrations and the gradual decrease in sulfate at the SMTZ reflect a series of biogeochemical processes resulting from the dissolution of carbonate and other minerals by AOM. The research indicates that sulfate in AOM may originate from multiple sources. Through analyzing the vertical distribution of shallow gas and the geochemical properties of pore water, this study elucidates the shallow gas formation mechanism and the features of the SMTZ, laying the groundwork for further investigations.

Structural/surface characterization of transition metal element–doped H-ZSM-5 adsorbent for CH3SH removal: identification of active adsorption sites and deactivation mechanism - Yuxuan Xie; Xiao Peng; Xin Song; Ping Ning; Xin Sun; Yixing Ma; Chi Wang; Kai Li (Environmental Science and Pollution Research, 2024)

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

Hepatotoxic of polystyrene microplastics in aged mice: Focus on the role of gastrointestinal transformation and AMPK/FoxO pathway - Pengfei Xie; Pengcheng Li; Xiaoshan Zhu; Deshan Chen; Mohammad Mehdi Ommati; Hongwei Wang; Lei Han; Shixiao Xu; Ping Sun (Science of The Total Environment, 2024)

Miocene Equisetum tubers from the Wulan Basin, Northeast Qinghai-Tibetan Plateau and their paleoecological significance - Zhen-Dong Cao; Peng Zhang; Si-Hang Zhang; Yi-Hong Yang; Jia-Yi Chen; Li-Ming Liu; Xiang-Chuan Li; San-Ping Xie (Palaeoworld, 2024)

Enhanced absorption of SO2 from phosphogypsum decomposition by phosphate slurry for phosphoric acid production - Wenmin Qian; Yanyu Yang; Zewei Liu; Jin Zhang; Xin Song; Nan Shi; Ming Xie; Bin Li; Ping Ning (Journal of Hazardous Materials, 2024)

Mediation of the JNC/ILC2 pathway in DBP-exacerbated allergic asthma: A molecular toxicological study on neuroimmune positive feedback mechanism - Xiaomin Xie; Yan Li; Biao Yan; Qi Peng; Runming Yao; Qihong Deng; Jinquan Li; Yang Wu; Shaohui Chen; Xu Yang; Ping Ma (Journal of Hazardous Materials, 2024)

Combined inhibitory effects of microcystin-LR and microcystin-RR on growth and development in zebrafish larvae - Xiao-chun Guo; Shao-yong Lu; Sheng-nan Zhang; Ping Xie; Guang-yu Li; Zu-qin Shi; Yi-tong Zhou; Yu-meng Wang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Dynamic, synergistic, and optimal emissions and kinetics of volatiles during co-pyrolysis of soil remediation plants with kaolin/modified kaolin - Zhibin Chen; Weijie Li; Shengzheng Huang; Ping Zhuang; Dajie Jia; Fatih Evrendilek; Sheng Zhong; Yoshihiko Ninomiya; Zuoyi Yang; Yao He; Wuming Xie; Jingyong Liu; et al. (Chemical Engineering Journal, 2024)

Charge-reversal biodegradable nanoplatform with ferroptosis and ICD induction for tumor synergistic treatment - Ping Sun; Li Huang; Zimu Li; Yao Yang; Shiman Lu; Nansha Gao; Hongzhong Chen; Xiaowei Zeng; Zhongjian Xie (Chemical Engineering Journal, 2024)

Iodine Acetonitrile as a Drinking Water Disinfectant Showed a Potential Toxic Effect on Organism - Ya-Ping Li; Jie-Wen Cai; Pin-Ying Su; Shi-Ming Xie; Jia-Xuan Lai; Zi-Ru Xian; Jing-Da Qiao (Water, Air, & Soil Pollution, 2024)

Thermocline stratification favors phytoplankton spatial overlap and species diversity in a subtropical deep reservoir - Li Wang; Jiarui Liu; Zhen Bao; Xufa Ma; Hong Shen; Ping Xie; Jun Chen (Science of The Total Environment, 2024)

Predictable shifts in diversity and ecosystem function in phytoplankton and zooplankton communities along thermocline stratification intensity continua - Li Wang; Jiarui Liu; Zhen Bao; Xufa Ma; Hong Shen; Jun Chen; Ping Xie (Science of The Total Environment, 2024)

Enhanced efficiency in two-terminal all-perovskite tandem solar cells via binary functional high polymer doping strategy - Ziang Xie; Sen Chen; Yili Pei; Li Li; Shiping Zhang; Ping Wu (Chemical Engineering Journal, 2024)

Integration of transcriptome and metabolome reveals the accumulation of related metabolites and gene regulation networks during quinoa seed development - Qianchao Wang; Jirong Shi; Junna Liu; Ping Zhang; Li Li; Heng Xie; Hanxue Li; Hongxin Wang; Chenghong Liu; Peng Qin (Plant Molecular Biology, 2024)

Introducing fluorescent probe technology for detecting microcystin-LR in the water and cells - Bingyan Li; Zhaomin Wang; Huiyan Chuan; Jing Li; Ping Xie; Yong Liu (Analytica Chimica Acta, 2024)

Particulate polycyclic aromatic hydrocarbons in rural households burning solid fuels in Xuanwei County, Southwest China: occurrence, size distribution, and health risks - Xinyu Han; Dingshuang Li; Wei Du; Jianwu Shi; Shuai Li; Yuqi Xie; Shihan Deng; Zhihao Wang; Senlin Tian; Ping Ning (Environmental Science and Pollution Research, 2024)

In situ biomass burning enhanced the contribution of biogenic sources to sulfate aerosol in subtropical cities - Tingting Li; Jun Li; Luhua Xie; Boji Lin; Hongxing Jiang; Rong Sun; Xiao Wang; Ben Liu; Chongguo Tian; Qilu Li; Wanglu Jia; Gan Zhang; et al. (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Visualization of microcystin-LR and sulfides in plateau lakes - Zhaomin Wang; Yu Hao; Jianping Shen; Bingyan Li; Huiyan Chuan; Ping Xie; Yong Liu (Journal of Hazardous Materials, 2024)

Analyzing sulfur cycle process in natural lakes based on the combination of sulfur-producing genes and fluorescence technology - Jianping Shen; Changhui Zhang; Jing Li; Yue Zhang; Yu Hao; Ping Xie; Zhe Chen; Yong Liu (Journal of Cleaner Production, 2024)

Multidentate anchoring strategy for synergistically modulating crystallization and stability towards efficient perovskite solar cells - Ping Hu; Wenbo Zhou; Junliang Chen; Xin Xie; Jingwei Zhu; Yuxin Zheng; Yafeng Li; Junming Li; Mingdeng Wei (Chemical Engineering Journal, 2024)

Corrigendum to ‘Microbiota assembly patterns and diversity of nine plateau lakes in Yunnan, southwestern China’ [Chemosphere 314 (2023) 137700] - Qi Liu; Fengqin Chang; Ping Xie; Yang Zhang; Lizeng Duan; Haoyu Li; Xiaonan Zhang; Yun Zhang; Donglin Li; Hucai Zhang (Chemosphere, 2023)

Chronic cadmium exposure triggered ferroptosis by perturbing the STEAP3-mediated glutathione redox balance linked to altered metabolomic signatures in humans - Ping Deng; Jingdian Li; Yonghui Lu; Rongrong Hao; Mindi He; Min Li; Miduo Tan; Peng Gao; Liting Wang; Huihui Hong; Jiawen Tao; Muxue Lu; et al. (Science of The Total Environment, 2023)

Anti-freezing hydrogel thermocells with confined microcrystallization for enhanced low-grade heat harvest - Ping-Fan Li; Ting-Yuan Hu; Tao Luo; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Da-Wei Pan; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Electronegative graphene film based interface-chemistry regulation for stable lithium metal batteries - Ping Xie; Yumeng Peng; Xianbin Liu; Binze Yang; Fan Yang; Haijie Zhao; Sayed Y. Attia; Xiaoming Xu; Yulong Sun; Yanhong Yin; Yesheng Li; Ziping Wu (Chemical Engineering Journal, 2023)

Multiscale information interaction at local frequency band in functional corticomuscular coupling - Shengcui Cheng; Xiaoling Chen; Yuanyuan Zhang; Ying Wang; Xin Li; Xiaoli Li; Ping Xie (Cognitive Neurodynamics, 2023)

SIRT3-dependent mitochondrial redox homeostasis mitigates CHK1 inhibition combined with gemcitabine treatment induced cardiotoxicity in hiPSC-CMs and mice - Jia-Wen Chen; Tian-Kai Shan; Tian-Wen Wei; Qi-Qi Jiang; Chong Du; Ling-Feng Gu; Tong-Tong Yang; Liu-Hua Zhou; Si-Bo Wang; Yu-Lin Bao; Hao Wang; Yong Ji; et al. (Archives of Toxicology, 2023)

Fast perception of rock mass strength and integrity in TBM tunnelling using in-situ penetration test - Wei-Qiang Xie; Xiao-Ping Zhang; Shao-Hui Tang; Xiao-Li Liu; Xin-Fang Li; Qi Zhang; Fa-Yuan Yan; Chen Xu; Quan-Sheng Liu (Tunnelling and Underground Space Technology, 2023)

Plastisphere characterization in habitat of the highly endangered Shinisaurus crocodilurus: Bacterial composition, assembly, function and the comparison with surrounding environment - Mujiao Xie; Mei Lv; Zhiwen Zhao; Linmiao Li; Haiying Jiang; Yepin Yu; Xiujuan Zhang; Ping Liu; Jinping Chen (Science of The Total Environment, 2023)

Environmental cadmium exposure facilitates mammary tumorigenesis via reprogramming gut microbiota-mediated glutamine metabolism in MMTV-Erbb2 mice - Yang Yue; Huadong Zhang; Ping Deng; Miduo Tan; Chengzhi Chen; Bo Tang; Jingdian Li; Fengqiong Chen; Qi Zhao; Ling Li; Rongrong Hao; Hui Wang; et al. (Science of The Total Environment, 2023)

Contribution of the bacterial community of poorly fermented oat silage to biogas emissions on the Qinghai Tibetan Plateau - Chaosheng Liao; Binbin Na; Xiaolong Tang; Man Zhao; Changbing Zhang; Shiyong Chen; Minghong You; Binqiang Bai; Lizhuang Hao; Dorjeeh Tondrob; Guangpeng Qu; Shuqing Yang; et al. (Science of The Total Environment, 2023)

Enhancing catalytic hydrolysis activity of ZnNiAl hydrotalcite-like compounds-derived oxides using rare earth metals - Kunlin Li; Yu Tian; Xie Tang; Peng Gao; Xiao Peng; Ping Ning; Chi Wang; Fei Wang; Xin Sun; Kai Li (Journal of Cleaner Production, 2023)

Co-application of chitooligosaccharides and arbuscular mycorrhiza fungi reduced greenhouse gas fluxes in saline soil by improving the rhizosphere microecology of soybean - Junqing Ma; Yi Xie; Jiali Sun; Ping Zou; Siqi Ma; Yuan Yuan; Shakeel Ahmad; Xia Yang; Changliang Jing; Yiqiang Li (Journal of Environmental Management, 2023)

Genetic variations of CYP3A4 on the metabolism of itraconazole in vitro - Sai-li Xie; Xiayan Zhu; Nanyong Gao; Qianmeng Lin; Chaojie Chen; Yun-jun Yang; Jian-ping Cai; Guo-xin Hu; Ren-ai Xu (Food and Chemical Toxicology, 2023)

Erratum to: Compound muscle action potential (CMAP) scan examination of paretic and contralateral muscles reveals motor unit alterations after stroke - Maoqi Chen; Zhiyuan Lu; Xiaoyan Li; Ya Zong; Qing Xie; Sheng Li; Ping Zhou (Science China Life Sciences, 2023)

Compound muscle action potential (CMAP) scan examination of paretic and contralateral muscles reveals motor unit alterations after stroke - Maoqi Chen; Zhiyuan Lu; Xiaoyan Li; Ya Zong; Qing Xie; Sheng Li; Ping Zhou (Science China Life Sciences, 2023)
This study presents a novel compound muscle action potential (CMAP) examination of motor unit changes in paretic muscle post stroke. CMAP scan of the first dorsal interosseous (FDI) muscle was performed bilaterally in 16 chronic stroke subjects. Various parameters were derived from the CMAP scan to examine paretic muscle changes, including CMAP amplitude, D50, step index (STEPIX) and amplitude index (AMPIX). A significant decrease in CMAP amplitude and STEPIX was observed in paretic muscles compared with contralateral muscles (CMAP amplitude: paretic (9.0±0.5) mV, contralateral (11.3±0.9) mV, P =0.024; STEPIX: paretic 101.2±7.6, contralateral 121.9±6.5, P =0.020). No significant difference in D50 and AMPIX was observed between the paretic and contralateral sides (P>0.05). The findings revealed complex paretic muscle changes including motor unit degeneration, muscle fiber denervation, reinnervation and atrophy, providing useful insights to help understand neuromuscular mechanisms associated with weakness and other functional deterioration post stroke. The CMAP scan experimental protocols and the applied processing methods are noninvasive, convenient, and automated, offering practical benefits for clinical application.

Photo-assisted “co-movement catalysis”: CoFe2O4/CNS heterojunction based portable electrochemical sensor for simultaneous detection of Pb2+ and Cd2+ in natural water - Fengqian Xie; Feng Tang; Xinli Li; Xiaoran Wu; Shujun Wang; Hongqiang Xie; Ping Wang; Yueyun Li; Qing Liu (Journal of Hazardous Materials, 2023)

CO oxidation over PdOσ/Fe1-xWxOy catalysts and their SO2 resistance at relatively low temperature - Jingyi Zhang; Jinding Chen; Zonglin Li; Huiling Weng; Yu Xie; Junjie Wen; Wenbiao Duan; Qiulin Zhang; Jianjun Chen; Ping Ning (Fuel, 2023)

Fermentation of Rosa roxburghii Tratt by Limosilactobacillus fermentum NCU001464: Physicochemical characteristics and biological activity - Hai-Li Zhou; Fei Peng; Jia-Xin Lin; Li-Ping Hu; Mingyong Xie; Tao Xiong (Food Bioscience, 2023)

Refining health risk assessment of arsenic in wild edible boletus from typical high geochemical background areas: The role of As species, bioavailability, and enterotoxicity - Mengying Li; Zheng Chen; Qing Xiong; Yunzhen Mu; Yumei Xie; Mengyan Zhang; Lena Q. Ma; Ping Xiang (Environmental Pollution, 2023)

Virtual screening for potential discoidin domain receptor 1 (DDR1) inhibitors based on structural assessment - Jiali Xie; Dan Meng; Yihao Li; Ruoyu Li; Ping Deng (Molecular Diversity, 2023)

An aggregation-induced emission sensor combined with UHPLC-Q-TOF/MS for fast identification of anticoagulant active ingredients from traditional Chinese medicine - Ziyi Li; Bing Wang; Kunhui Sun; Guo Yin; Ping Wang; Xie-an Yu; Chaofeng Zhang; Jiangwei Tian (Analytica Chimica Acta, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Reduction and adsorption of uranium(VI) from aqueous solutions using nanoscale zero-valent manganese - Xiaohan Li; Juanxi Huang; Zhengqin Shi; Yuan Xie; Zhengfan Xu; Jianyou Long; Gang Song; Yaxuan Wang; Gaosheng Zhang; Xiatiao Luo; Ping Zhang; Shuxiang Zha; et al. (Journal of Environmental Management, 2023)

Effect of safflower oil and magnetic field-modified soy 11S globulin on rheological and emulsifying properties of oil-in-water emulsions - Zhuang-Li Kang; Jing-jie Xie; Zhong-liang Hu; Yan-ping Li; Han-Jun Ma (Food Hydrocolloids, 2023)

COS and H2S simultaneous removal from blast furnace gas over a tailored Cu/Zr co-doped K@TiO2 bifunctional catalyst under low temperature - Xiang Li; Xueqian Wang; Li Yuan; Langlang Wang; Yixing Ma; You Wu; Yibing Xie; Rui Cao; Yiran Xiong; Ping Ning (Chemical Engineering Journal, 2023)

PM2.5/PM10-bound PAHs in Hotan city: Concentrations, sources, and contribution to ·OH - Xiaohui Zhang; Dilinuer Talifu; Xiang Ding; Xinming Wang; Kejun Li; Bowen Liu; Qilong Zhao; Ping Luo; Xiaoxia Xie (Atmospheric Environment, 2023)

Transfer of Se from sediments to the western mosquitofish Gambusia affinis: Tissue distribution, accumulation, and effects on the antioxidant physiology - Ping Liu; Dan Li; Feifan Wang; Lingtian Xie; Hongxing Chen (Aquatic Toxicology, 2023)

MLK3 localizes mainly to the cytoplasm and promotes oxidative stress injury via a positive feedback loop - Yu Jiang; Bai-Xue Wang; Yi Xie; Li Meng; Meng Li; Cai-Ping Du (Cell Biochemistry and Biophysics, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

A meta-analysis on the toxicity of microcystin-LR to fish and mammals - Huixia Zhang; Xu Zhao; Yehao Li; Ping Xie (Environmental Pollution, 2023)

Transcriptomics integrated with metabolomics unravels the interweaving of inflammatory response and 1-stearoyl-2-arachidonoyl-sn-glycerol metabolic disorder in chronic cadmium exposure-induced hepatotoxicity - Rongrong Hao; Heng Xiao; Hui Wang; Ping Deng; Yang Yue; Jingdian Li; Yan Luo; Li Tian; Jia Xie; Mengyan Chen; Zhou Zhou; Fengqiong Chen; et al. (Environmental Toxicology and Pharmacology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

Fluorescence enhancement of surface plasmon coupled emission by Au nanobipyramids and its modulation effect on multi-wavelength radiation - Kai-Xin Xie; Rui-Ping Huo; Xiu-Li Song; Qiao-Ling Liu; Yue Jiang; Yu-Han Li; Lu-Lu Dong; Jia-Xin Cheng (Analytica Chimica Acta, 2023)

Different dietary fibers unequally remodel gut microbiota and charge up anti-obesity effects - Jia-Jia Wen; Ming-Zhi Li; Jie-Lun Hu; Jiang Wang; Zhi-Qiang Wang; Chun-Hua Chen; Jing-Rui Yang; Xiao-Jun Huang; Ming-Yong Xie; Shao-Ping Nie (Food Hydrocolloids, 2023)

CircBLNK regulates tumor proliferation and apoptosis by miR-578/ING5 axis in non-small cell lung cancer - Ping Li; Liuyi Zou; Zuojun Luo; Yuhua Lu; Shuang Yu; Yujun Zhu; Yong Xie (Molecular & Cellular Toxicology, 2023)

Correction to: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2023)

Fluorescence Properties and Chemical Composition of Fine Particles in the Background Atmosphere of North China - Ping Li; Siyao Yue; Xiaoyang Yang; Di Liu; Qiang Zhang; Wei Hu; Shengjie Hou; Wanyu Zhao; Hong Ren; Gang Li; Yuanguan Gao; Junjun Deng; et al. (Advances in Atmospheric Sciences, 2023)

Real-time perception of rock–machine interaction information in TBM tunnelling using muck image analysis - Wei-Qiang Xie; Xiao-Ping Zhang; Xiao-Li Liu; Chen-Yu Xu; Xin-Fang Li; Dan-Qing Song; Qing Ma; Nan Hu (Tunnelling and Underground Space Technology, 2023)

Meta-analysis reveals cyanotoxins risk across African inland waters - Xu Zhao; Ying Liu; Yu-Ming Guo; Chi Xu; Liang Chen; Geoffrey A. Codd; Jun Chen; Ying Wang; Pu-Ze Wang; Li-Wei Yang; Long Zhou; Yan Li; et al. (Journal of Hazardous Materials, 2023)

Environmentally relevant level of perfluorooctanoic acid affect the formation of aerobic granular sludge - Zhouyun Xie; Ni Zhang; Guojing Yang; Qiuxiang Xu; Dongbo Wang; Li Tang; Jingfen Xia; Ping Li; Xiaoming Li (Journal of Environmental Management, 2023)

Ultra-low concentration terbium (Tb) adsorption on garlic peels biosorbent and its application for Nd-Fe-B scraps recovery - Qingqing Chang; Ping Li; Yunwu Han; Xindi Guan; Jiachun Xiong; Qian Li; Hailin Zhang; Kai Huang; Xin Zhang; Haijiao Xie; Tao Qi (Journal of Environmental Chemical Engineering, 2023)

Structured lipids produced from palm-olein oil by interesterification: A controllable lipase-catalyzed approach in a solvent-free system - Hongzeng Ai; Yee-Ying Lee; Xiaodong Xie; Chin Ping Tan; Oi Ming Lai; Aijun Li; Yong Wang; Zhen Zhang (Food Chemistry, 2023)

Effect of co-inoculation of Lactobacillus plantarum and Lentilactobacillus buchneri on aerobic stability and microbial community composition of perennial sorghum silage - Maoya Li; Shufeng Zhou; Xiaolong Tang; Chaosheng Liao; Ping Li; Yixiao Xie; Qiming Cheng; Chao Chen (Biomass and Bioenergy, 2023)

Optimizing human endometrial mesenchymal stem cells for maximal induction of angiogenesis - Jie Zhang; Huifang Song; Xuemei Fan; Sheng He; Wenjuan Yin; Zexu Peng; Xiaoyan Zhai; Kun Yang; Hui Gong; Zhijun Wang; Yi Ping; Sanyuan Zhang; et al. (Molecular and Cellular Biochemistry, 2023)

Carp stocking and climate change are potentially more important factors than nutrient enrichment driving water quality deterioration in subtropical freshwater lakes in China - Haojie Su; Jianfeng Chen; Yun Li; Qingyang Rao; Congqiang Luo; Xuwei Deng; Hong Shen; Renhui Li; Jun Chen; Yuanfeng Sun; Jiamin Pan; Suhui Ma; et al. (Limnology and Oceanography, 2023)
Freshwater lakes across the world have undergone dramatic changes in biological components and water quality over the past several decades. Previous studies focused on potential drivers mainly on nutrient enrichment in the catchment. However, the relative importance of climate change and the top‐down cascade effects of fish stocking on water quality is not fully understood. Here, by compiling 155 lakes data with four periods of field investigation in subtropical lakes in China, we found no significant changes in water total nitrogen and total phosphorus in the past two decades. However, the phytoplankton abundance increased significantly, and the water clarity declined by 44.1%. We further found that carp stocking and climate change are potentially more important than nutrients driving water quality change, which is also evidenced in two lakes (Lake Donghu and Qiandao) with long‐term monitoring histories. Specifically, carp stocking can decrease the water clarity directly by stirring up sediment and indirectly by trophic cascade along the food web. For climatic factors, mean annual temperature (MAT) has a positive effect on phytoplankton abundance, while mean annual precipitation has a negative one, with climates overall having little effect on water clarity. In addition, nutrient enrichment and climate change also have strong interactions with carp stocking, which may enhance the top‐down effects on water quality. Our findings highlight that either MAT or carp stocking may become an overwhelming driver of water clarity decline, which provides new insights into the conservation strategy for water quality management in the subtropical lakes in China.

Transcatheter closure of perimembranous ventricular septal defect using a novel fully bioabsorbable occluder: multicenter randomized controlled trial - Shouzheng Wang; Zefu Li; Yunbing Wang; Tianli Zhao; Xuming Mo; Taibing Fan; Jianhua Li; Tao You; Rundi Deng; Wenbin Ouyang; Weiwei Wang; Chuangnian Zhang; et al. (Science Bulletin, 2023)

Southern Ocean warming and its climatic impacts - Wenju Cai; Libao Gao; Yiyong Luo; Xichen Li; Xiaotong Zheng; Xuebin Zhang; Xuhua Cheng; Fan Jia; Ariaan Purich; Agus Santoso; Yan Du; David M. Holland; et al. (Science Bulletin, 2023)

Identification of Heterophilic Epitopes of H1N1 Influenza Virus Hemagglutinin - Jing-ying Sun; Chun-yan Guo; Guo-rong Wang; Li-ting Yan; Qing Feng; Yan Li; Xue-ping Huo; Xin Xie; Jun Hu; Li-jun Sun (Current Microbiology, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Preparation and characterization of carboxymethyl chitosan/pullulan composite film incorporated with eugenol and its application in the preservation of chilled meat - Zhen Zeng; Yu-Jing Yang; Qian Tu; Yu-Ying Jian; Da-Ming Xie; Ting Bai; Shan-Shan Li; Yun-Tao Liu; Cheng Li; Cai-Xia Wang; Ai-Ping Liu (Meat Science, 2023)

Effects of pre-emulsified safflower oil with magnetic field modified soy 11S globulin on the gel, rheological, and sensory properties of reduced-animal fat pork batter - Zhuang-Li Kang; Jing-jie Xie; Yan-ping Li; Wan-jie Song; Han-Jun Ma (Meat Science, 2023)

Magnetic field assisted enhancement of electronic metal-support interactions in FexCuy@TiO2-δ catalysts for arsine catalytic oxidation - Yibing Xie; Xueqian Wang; Ping Ning; Langlang Wang; Yixing Ma; Yuan Li; Rui Cao; Hui Zhang; Xiang Li; Bowen Xu (Journal of Cleaner Production, 2023)

Advantageous Role of N-doping on K@Al in COS/CS2 Hydrolysis: Diminished Oxygen Mobility and Rich basic sites - Rui Cao; Xueqian Wang; Ping Ning; Yibing Xie; Langlang Wang; Yixing Ma; Xiang Li; Hui Zhang; Jingye Liu (Fuel, 2023)

Quality assessment of variable collagen tissues of sea cucumber (Stichopus japonicus) body wall under different heat treatment durations by label-Free proteomics analysis - Yi-Zhen Huang; Yi-Sha Xie; Yan-Xin Li; Mei-Yu Zhao; Na Sun; Hang Qi; Xiu-Ping Dong (Food Research International, 2023)

Microbiota assembly patterns and diversity of nine plateau lakes in Yunnan, southwestern China - Qi Liu; Fengqin Chang; Ping Xie; Yang Zhang; Lizeng Duan; Haoyu Li; Xiaonan Zhang; Yun Zhang; Donglin Li; Hucai Zhang (Chemosphere, 2023)

Resource utilization of hazardous solid waste blast furnace dust: Efficient wet desulfurization and metal recovery - Xuejin Yang; Binghua Xie; Fang Wang; Ping Ning; Kai Li; Lijuan Jia; Jiayu Feng; Futing Xia (Chemosphere, 2023)

Integrated physiological, biochemical, and transcriptomic analysis of thallium toxicity in zebrafish (Danio rerio) larvae - Xinrong Wei; Xiao Li; Ping Liu; Lixia Li; Hongxing Chen; Dan Li; Juan Liu; Lingtian Xie (Science of The Total Environment, 2023)

Long-term cadmium exposure impairs cognitive function by activating lnc-Gm10532/m6A/FIS1 axis-mediated mitochondrial fission and dysfunction - Ping Deng; Huadong Zhang; Liting Wang; Sheng Jie; Qi Zhao; Fengqiong Chen; Yang Yue; Hui Wang; Li Tian; Jia Xie; Mengyan Chen; Yan Luo; et al. (Science of The Total Environment, 2023)

Coupling and environmental implications of in situ formed biogenic Fe–Mn minerals induced by indigenous bacteria and oxygen perturbations for As(III) immobilization in groundwater - Xinxin Zhao; Zuoming Xie; Taikun Liu; Ping Li; Fuwen Pei; Linan Wang (Science of The Total Environment, 2023)

First discovery of biodegraded petroleum in the South Qilian Basin, Northwest China: Implications for the origin of gas hydrates - Furong Tan; Yang Li; Yigui Han; Guochun Zhao; Shiming Liu; Fangpeng Du; Zhiqing Xie; Ping Lu (Journal of Asian Earth Sciences, 2023)

Effects of polystyrene nanoplastics on the physiological and biochemical characteristics of microalga Scenedesmus quadricauda - Ru-ru Li; Bin-liang Wang; Fang-ru Nan; Jun-ping Lv; Xu-dong Liu; Qi Liu; Jia Feng; Shu-lian Xie (Environmental Pollution, 2023)

Acute exposure to microcystins affects hypothalamic-pituitary axes of male rats - Ting Shi; Lin-Lin Xu; Liang Chen; Jun He; Ye-Ke Wang; Feng Chen; Yang Chen; John P. Giesy; Yu-Ting Wang; Qian-Hui Wu; Wen-Li Xu; Jun Chen; et al. (Environmental Pollution, 2023)

Efficient fabrication of desert beetle-inspired micro/nano-structures on polypropylene/graphene surface with hybrid wettability, chemical tolerance, and passive anti-icing for quantitative fog harvesting - Wei-long Zhou; Ting Wu; Yu Du; Xiao-hu Zhang; Xin-chang Chen; Jin-bo Li; Heng Xie; Jin-ping Qu (Chemical Engineering Journal, 2023)

Potential for volatile fatty acid production via anaerobically-fermenting rice straw pretreated with silage effluent and phenyllactic acid - Hong Sun; Chaosheng Liao; Liangyin Chen; Qiming Cheng; Yulong Zheng; Chunmei Wang; Yixiao Xie; Chao Chen; Ping Li (Bioresource Technology, 2023)

Catalysts for gaseous organic sulfur removal - Yuxuan Xie; Jiacheng Bao; Xin Song; Xin Sun; Ping Ning; Chi Wang; Fei Wang; Yixing Ma; Maohong Fan; Kai Li (Journal of Hazardous Materials, 2023)

Enhancing flotation removal of unburned carbon from fly ash by coal tar-based collector: Experiment and simulation - Kanghao Zheng; Wenjun Zhang; Yijiang Li; An Ping; Feng Wu; Guangyuan Xie; Wencheng Xia (Fuel, 2023)

Enhanced stability and combustion performance of AlH3 in combination with commonly used oxidizers - Ming-Hui Yu; Su-Lan Yang; Wu-Xi Xie; Zhao-Yang Zhu; He-Ping Li; Qi-Long Yan (Fuel, 2023)

Salt Bridge-intermediated three phase decoupling electrolytes for high voltage electrolytic aqueous Zinc-Manganese dioxides battery - Qi Xu; Qi-Xing Xie; Tong Xue; Gao Cheng; Jian-Dong Wu; Lan Ning; Xiang-Hui Yan; You-Jun Lu; Zhong-Li Zou; Bei-Ping Wang; Feng-Lan Han (Chemical Engineering Journal, 2023)

Highly conductive, stretchable, durable, breathable electrodes based on electrospun polyurethane mats superficially decorated with carbon nanotubes for multifunctional wearable electronics - Guoxi Luo; Jiaqi Xie; Jielun Liu; Qiankun Zhang; Yunyun Luo; Min Li; Wenke Zhou; Ke Chen; Zhikang Li; Ping Yang; Libo Zhao; Kwok Siong Teh; et al. (Chemical Engineering Journal, 2023)

An antibody cocktail with broadened mutational resistance and effective protection against SARS-CoV-2 - Chunyun Sun; Hang Chi; Fei Yuan; Jing Li; Ji Yang; Aihua Zheng; Fei Wang; Lingling Sun; Yanjing Zhang; Ping Hu; Lihua Jiao; Yongqiang Deng; et al. (Science China Life Sciences, 2023)

Abietane diterpenoids with neuroprotective activities from Phlegmariurus carinatus - Yang Liu; Qiang Wang; Dong-Kun Zheng; De Zhang; Zhen Xie; Jia-Wei Hu; Xin-Hua Xie; Jing Li; Shu-Ping Jiang (Natural Product Research, 2022)

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Association between gestational arsenic exposure and intrauterine growth restriction: the role of folate content - Fei-Xiang Xu; Xu Chen; Heng Zhang; Yi-Jun Fan; Ya-Ping Song; Jin-Wei Lv; Ya-Li Xie; Yichao Huang; Dao-Zhen Chen; Hua Wang; De-Xiang Xu (Environmental Science and Pollution Research, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Monoterpenoid indole alkaloids with potential neuroprotective activities from the stems and leaves of Melodinus cochinchinensis - Yu-Jie Li; Juan Li; Lan Xie; Jun-Yu Zhou; Qiu-Xuan Li; Rui-Yuan Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2022)

Feasibility Studies of Nebulized SARS-CoV-2 Neutralizing Antibody in Mice and Cynomolgus Monkeys - Jilei Jia; Zhaojuan Yin; Xiao Zhang; Huimin Li; Dan Meng; Qianqian Liu; Hongfang Wang; Meng Han; Shixiang Suo; Yan Liu; Ping Hu; Chunyun Sun; et al. (Pharmaceutical Research, 2022)
Purpose Neutralizing antibodies, administrated through intravenous infusion, have shown to be highly efficacious in treating mild and moderate COVID-19 caused by SARS-CoV-2 infection in the lung. However, antibodies do not transport across the plasma-lung barrier efficiently, and up to 100 mg/kg dose was used in human causing significant supply and cost burdens. This study was to explore the feasibility of nebulized antibodies inhalation delivery as an alternative route. Methods HB27, a potent RBD-specific humanized monoclonal antibody (Zhu et al. in National Sci Rev. 8:nwaa297, 2020), showed excellent protection against SARS-CoV-2 in animal model and good safety profile in clinical studies. The pharmacokinetics and preliminary safety of HB27 administrated through the respiratory tract were studied in mice and cynomolgus monkeys here. Results At a single 5 mg/kg dose, the peak HB27 concentration in mice pulmonary epithelial lining fluid (ELF) reached 857.8 μg/mL, 670-fold higher than the PRNT 90 value of 1.28 μg/mL, and maintained above PRNT 90 over 240 h. In contrast, when administrated by intravenous injection at a 5 mg/kg dose, the antibody concentrations in mice ELF were below PRNT 90 value throughout, and were about 50-fold lower than that in the serum. In cynomolgus monkeys administrated with a single dose through inhalation, the antibody concentration in ELF remained high within 3 days. No drug-related safety concerns were observed in the studies. Conclusions The study demonstrated that nebulized neutralizing antibody delivery though inhalation could be a more efficient and efficacious alternative approach for treating COVID-19 and other respiratory infectious diseases, and warrants further evaluation in clinical studies.

Bio-organic Fertilizer with Bacillus subtilis F2 Promotes Strawberry Plant Growth and Changes Rhizosphere Microbial Community - Li Liu; Xiang Li; Tianyu Li; Yuan Xie; Zhuoyang Cao; Ping Fang (Journal of Soil Science and Plant Nutrition, 2022)

Oxytocin Receptor in Cerebellar Purkinje Cells Does Not Engage in Autism-Related Behaviors - Li-Ping Shen; Wei Li; Ling-Zhu Pei; Jun Yin; Shu-Tao Xie; Hong-Zhao Li; Chao Yan; Jian-Jun Wang; Qipeng Zhang; Xiao-Yang Zhang; Jing-Ning Zhu (The Cerebellum, 2022)

Effects of Involuntary and Voluntary Exercise in Combination with Acousto-Optic Stimulation on Adult Neurogenesis in an Alzheimer's Mouse Model - Wan-yi Li; Jun-yan Gao; Su-Yang Lin; Shao-tao Pan; Biao Xiao; Yu-tao Ma; Kai Xie; Wei Shen; Zhi-tao Liu; Guang-yu Li; Jie-jie Guo; Qin-wen Wang; et al. (Molecular Neurobiology, 2022)

Dominant Fungal Epiphytes Promote Growth of the Invasive Plant Ipomoea cairica Through Hormone Interactions - Hua Xu; Ping Chang; Shaoshan Li; Jianguo Lu; Xuejun Lin; Can Xie (Journal of Plant Growth Regulation, 2022)

Trichocladabiflavone A, a chalcone-flavonone type biflavonoid from Selaginella trichoclada Alsto - Yang Xie; Xiao-Chang Yao; Lei-Hong Tan; Hong-Ping Long; Ping-Sheng Xu; Jing Li; Gui-Shan Tan (Natural Product Research, 2022)

Fine mapping of powdery mildew resistance gene MlWE74 derived from wild emmer wheat (Triticum turgidum ssp. dicoccoides) in an NBS-LRR gene cluster - Keyu Zhu; Miaomiao Li; Haibin Wu; Deyun Zhang; Lingli Dong; Qiuhong Wu; Yongxing Chen; Jingzhong Xie; Ping Lu; Guanghao Guo; Huaizhi Zhang; Panpan Zhang; et al. (Theoretical and Applied Genetics, 2022)

Preparation and In Vitro and In Vivo Evaluation of a Testosterone Film Forming Gel for the Treatment of Hypoactive Sexual Desire Disorder in Women - Jia Zeng; Tan-Fang Xie; Ting Huang; Fang Li; Zhi-Ping Wang; Ling-Lin Feng (AAPS PharmSciTech, 2022)

Detection of Microcystin-LR in the Cells and Natural Lake Water Samples by A Unique Fluorescence-Based Method - Yipeng Liu; Bingyan Li; Huixia Zhang; Yong Liu; Ping Xie (Journal of Fluorescence, 2022)

Is Zooplankton Body Size an Indicator of Water Quality in (Sub)tropical Reservoirs in China? - Li Wang; Jun Chen; Haojie Su; Xufa Ma; Zhixu Wu; Hong Shen; Jia Yu; Jiarui Liu; Yao Wu; Guangyi Ding; Ping Xie (Ecosystems, 2022)

Intelligent prediction of coal mine water inrush based on optimized SAPSO-ELM model under the influence of multiple factors - Yong-gang Zhang; Yuan-lun Xie; Li-ning Yang; Rao-ping Liao; Tao Qiu (Arabian Journal of Geosciences, 2022)
Mine water inrush is affected by many factors such as geological structure and fracture zone. However, there may be overlap among these factors, leading to uncertainty, fuzzy similarity and nonlinear relationship among most of them. Therefore, the traditional mathematical model is not ideal to predict water inrush. This paper proposes an intelligent model for predicting water inrush from coal floor based on simulated annealing particle swarm optimization-extreme learning machine (SAPSO-ELM). Based on 144 groups of learning data and 36 groups of predictive validation data, the proposed model extracted common factors from 14 geological factors that might be related to water inrush in a mining area, so as to reduce information interaction among discriminant indexes. In this paper, simulated annealing particle swarm optimization (SAPSO) is innovatively used to optimize the model parameters and compared with other intelligent models (SVM, BPNN, PSO-ELM and ELM) for the learning prediction of the same data. The results show that the common factors extracted from the original variables contain most of the comprehensive information and can reduce information redundancy. Compared with traditional intelligent models (SVM, BPNN, PSO-ELM and ELM), the proposed model improves the computational efficiency of convergence, and the prediction accuracy is higher. It is proved that SAPSO-ELM intelligent algorithm is indeed scientific and has broad application prospect in result prediction induced by complex multi-factors.

Corrigendum: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2022)

Oxidative degradation/mineralization of dimethyl phthalate (DMP) from plastic industrial wastewater using ferrate(VI)/TiO2 under ultraviolet irradiation - Ping Wang; Yi Ding; Liting Zhu; Yunhao Zhang; Sijie Zhou; Linbei Xie; Ao Li (Environmental Science and Pollution Research, 2022)

Correction to: Proteasome-dependent inactivation of Akt is essential for 12-O-tetradecanoylphorbol 13-acetate-induced apoptosis in vascular smooth muscle cells - Yongna Fan; Ping Xie; Hua Zhang; Shubin Guo; Dongfeng Gu; Mingpeng She; HuiHua Li (Apoptosis, 2022)

Eutrophication and predation mediate zooplankton diversity and network structure - Yun Li; Rong Wang; Haojie Su; Jianjun Wang; Ping Xie; Feizhou Chen (Limnology and Oceanography, 2022)
Anthropogenic activities such as eutrophication and fishing have prominent effects on freshwater ecosystems. However, the ways in which ecosystem function and biodiversity respond to multiple drivers from eutrophication and top‐down predation remains inconclusive. We studied zooplankton communities in 102 subtropical shallow lakes in the eastern plain of China and further examined the joint effects of nutrient enrichment and predation on biodiversity and ecological networks. We found that alpha diversity was negatively influenced by nutrient conditions (such as total phosphorus and total nitrogen [TN]), whereas beta diversity (β‐diversity) was positively related to nutrients and was also structured by omnivorous fish showing a unimodal pattern. Furthermore, the network skewness of zooplankton increased with nutrient enrichment, especially TN, and was negatively related to omnivorous fish. This skewness is more sensitive than β‐diversity, whereas negative skew is primarily caused by omnivorous fish. Our results demonstrated that top‐down effects were dominant for zooplankton communities and resulted in structural adjustment of zooplankton communities, mainly with an increase in fish predation. A negative skewed network indicates the presence of more generalist species and stronger connections among the zooplankton assemblages, as well as decreased β‐diversity.

Estimating the added value of GRACE total water storage and uncertainty quantification in seasonal streamflow forecasting - Li Liu; Jingkai Xie; Haiting Gu; Yue-Ping Xu (Hydrological Sciences Journal, 2022)

A contribution to knowledge of Gyroporus (Gyroporaceae, Boletales) in China: three new taxa, two previous species, and one ambiguous taxon - Hui-Jing Xie; Li-Ping Tang; Man Mu; Yu-Guang Fan; Shuai Jiang; Ming-Sheng Su; Zhi-Qun Liang; Nian-Kai Zeng (Mycological Progress, 2022)

External evaluation of published population pharmacokinetic models of polymyxin B - Ya-qian Li; Kai-feng Chen; Jun-jie Ding; Hong-yi Tan; Nan Yang; Ya-qi Lin; Cui-fang Wu; Yue-liang Xie; Guo-ping Yang; Jing-Jing Liu; Qi Pei (European Journal of Clinical Pharmacology, 2021)

The chemical profile and biological activity of different extracts of Sapindus mukorossi Gaertn. against Cutibacterium acnes - Min-Ping Wei; Jin-Dan Qiu; Lu Li; Yun-Fei Xie; Ya-Hui Guo; Hang Yu; Yu-Liang Cheng; He Qian; Wei-Rong Yao (Natural Product Research, 2021)

Geo-structures and deformation-failure characteristics of rockslide areas near the Baige landslide scar in the Jinsha River tectonic suture zone - Shi-lin Zhang; Yue-ping Yin; Xie-wen Hu; Wen-pei Wang; Zong-liang Li; Xin-ming Wu; Gang Luo; Sai-nan Zhu (Landslides, 2021)

Two new biflavanoids from Selaginella trichoclada Alsto - Yang Xie; Ping-Sheng Xu; Kang-Ping Xu; Zhen-Xing Zou; Gan Zhou; Dai Li; Dan Li; Xiao-Min Li; Jing Li; Gui-Shan Tan (Natural Product Research, 2021)

Characterization of a novel shrimp pathogen, Vibrio brasiliensis , isolated from Pacific white shrimp, Penaeus vannamei - Ge Li; Guosi Xie; Hailiang Wang; Xiaoyuan Wan; Xinshu Li; Chengyin Shi; Ziyan Wang; Miao Gong; Ting Li; Ping Wang; Qingli Zhang; Jie Huang (Journal of Fish Diseases, 2021)
A novel pathogenic strain Vibrio 20190611023 was isolated from the hepatopancreas of moribund cultured Penaeus vannamei suffering from black gill disease. This strain was identified as V . brasiliensis based on the phylogenetic analyses of 16S rDNA gene and five other housekeeping genes (i.e., gapA , ftsZ , mreB , topA and gyrB ). Some biochemical features of this strain were determined with an API 20NE system, and its haemolytic activity was determined using a sheep blood agar plate. The pathogenicity of this isolate 20190611023 was confirmed by the experimental challenge tests and histopathological examinations. P. vannamei were challenged via reverse gavage with different doses of bacterial suspensions. The calculated median lethal dose (LD 50 ) was (3.16 ± 1.78) × 10 5 CFU/g (body weight). Moreover, antibiotic susceptibility tests were performed, the results of which showed that the strain 20190611023 was sensitive to chloramphenicol, compound sulphamethoxazole, ciprofloxacin, doxycycline and oxacillin, but resistant to erythromycin, kanamycin, gentamicin, cefoperazone, ceftriaxone, cefamezin and piperacillin. To our knowledge, this is the first report for demonstrating V . brasiliensis as a shrimp pathogen, which expands the host range of V . brasiliensis infection. The present study highlights that more attention should be paid to this novel pathogen in intensive shrimp aquaculture.

Cross-frequency and iso-frequency estimation of functional corticomuscular coupling after stroke - Ping Xie; Xiaohui Pang; Shengcui Cheng; Yuanyuan Zhang; Yinan Yang; Xiaoli Li; Xiaoling Chen (Cognitive Neurodynamics, 2021)

Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2021)

Synthesis and antitumor evaluation of (aryl)methyl-amine derivatives of dehydroabietic acid-based B ring-fused-thiazole as potential PI3K/AKT/mTOR signaling pathway inhibitors - Nai-Yuan Chen; Yu-Lan Xie; Guo-Dong Lu; Fang Ye; Xin-Yu Li; Yu-Wen Huang; Ming-Li Huang; Tie-Yu Chen; Cui-Ping Li (Molecular Diversity, 2021)

miR-20a Promotes the Axon Regeneration of DRG Neurons by Targeting Nr4a3 - Lili Zhao; Leilei Gong; Ping Li; Jing Qin; Lingchi Xu; Qiyao Wei; Huimin Xie; Susu Mao; Bin Yu; Xiaosong Gu; Songlin Zhou (Neuroscience Bulletin, 2021)

Evaluation of climate model simulations in representing the precipitation non‐stationarity by considering observational uncertainties - Yongjing Wan; Jie Chen; Ping Xie; Chong‐Yu Xu; Daiyuan Li (International Journal of Climatology, 2021)
The reliability of climate model simulations in representing the precipitation changes is one of the preconditions for climate‐change impact studies. However, the observational uncertainties hinder the robust evaluation of these climate model simulations. The goal of the present study is to evaluate the capacities of climate model simulations in representing the precipitation non‐stationarity in consideration of observational uncertainties. The mean of multiple observations from five observational precipitation datasets is used as a reference to quantify the uncertainty of observed precipitation and to evaluate the performance of climate model simulations. The non‐stationarity of precipitation was represented using the mean and variance of annual total precipitation and annual maximum daily precipitation for the 1982–2015 period. The results show that the spatial distributions of annual and extreme precipitation are similar for various observational datasets, while there has less agreement in the variance changes of extreme precipitation. Climate models are capable of representing the spatial distributions of the annual and extreme precipitation amounts at the global scales. In terms of the non‐stationarity, climate model simulations are capable of capturing the large‐scale spatial pattern of the trend in mean for annual precipitation. On the contrary, the simulations are less reliable in reproducing the change of extreme precipitation, as well as the trend of variance for annual precipitation. Overall, climate models are more reliable in simulating the mean of precipitation than the variance, and they are more reliable in simulating annual precipitation than extreme. Besides, the uncertainties of precipitation for both observations and simulations are much larger in monsoon regions than in other regions. This study suggests that considering observational uncertainties is necessary when using observational datasets as the reference to project future climate change and assess the impact of climate change on environments.

Analysis of loess landslide mechanism and numerical simulation stabilization on the Loess Plateau in Central China - Wan-li Xie; Qianyi Guo; Jason Y. Wu; Ping Li; Hui Yang; Maosheng Zhang (Natural Hazards, 2021)
Loess landslides have complicated deformation mechanisms. Accurately describing the internal failure deformation of loess landslides and establishing a theoretical method of landslide instability evaluation for the prevention of subsequent landslides have become important topics in western development project construction in China. This paper presents a case study of the Zhonglou Mountain landslide in Shaanxi Province, China. Based on field investigation results, a two-dimensional stability analysis model was constructed using the finite element method. Taking the deformation characteristics of the landslide as the research basis, the distribution laws of the displacement, stress, and shear strain of this landslide were identified with the strength reduction finite element numerical simulation method. Additionally, the safety factor was evaluated under normal and storm conditions. The numerical simulation results show that the horizontal tensile stress of the landslide was mainly distributed in the middle and upper parts of the landslide under normal conditions, while the vertical tensile stress was distributed near the sliding surface. Under heavy rainfall, the sliding force increased, and the anti-sliding force and anti-sliding section decreased; the location of the maximum shear strain shifted down from the middle and upper parts of the landslide body to the area with a shear crack, and the plastic shear strain area expanded along nearly the entire the sliding surface, leading to the occurrence of a landslide. Thus, the use of anti-slide piles to stabilize the landslide was proposed and tested. Monitoring points were arranged along the sliding surface to evaluate the displacement, stress, and strain responses. The on-site observation results agreed with the modeling results. The use of anti-slide piles was demonstrated to be an effective stabilization method for the Zhonglou Mountain landslide.

Identification of Colletotrichum brevisporum causing fruit rot in yellow passion fruit (Passiflora edulis f. flavicarpa) in China - Fang Qiu; Xi Li; Chang Ping Xie; Jing Li; Fei Qing Zheng (Australasian Plant Pathology, 2021)

The role of MYB proto-oncogene like 2 in tamoxifen resistance in breast cancer - Xia Li; Xi Zhang; Cong-Cong Wu; Ping-Ping Li; Yi-Mou Fu; Li-Hua Xie; Shuang-Shuang Sun; Ying-Ying Zhou; Bao-Ling Zhu (Journal of Molecular Histology, 2021)

How well do the ERA‐Interim , ERA ‐5, GLDAS ‐2.1 and NCEP‐R2 reanalysis datasets represent daily air temperature over the Tibetan Plateau? - Li Liu; Haiting Gu; Jingkai Xie; Yue‐Ping Xu (International Journal of Climatology, 2021)
Snow and glacier are important components in the hydrological cycle of the Tibetan Plateau (TP). Air temperature, as the main driver in freezing and thawing processes, becomes vital for hydrological modelling and prediction in this region. Due to a sparse ground gauging network, spatial density of air temperature measurement is insufficient for hydro‐meteorological studies. Therefore, the aim of this study is to identify the best representative temperature data for hydrological applications from four widely used reanalysis products, including ERA‐Interim, ERA‐5, GLDAS‐2.1 and NCEP‐R2, with reference to in situ measurements and gridded snow depth from the year 2008–2017 over the entire TP. To reduce errors, Bayesian Joint Probability (BJP) approach based on K‐Nearest Neighbour (KNN) classification algorithm (KNN‐BJP) is proposed to post‐process gridded reanalyses. The results indicate that all the reanalysis datasets provide highly correlated but cold biased air temperature. The correlation ecoefficiency is greater than 0.85. The cold biases are near −3 ° C and mainly distributed in the southeastern TP. Bias in daily maximum temperature during Spring is greater than −8 ° C for most stations. ERA‐Interim is found to have the closest agreement with in situ measurements, closely followed by GLDAS‐2.1. KNN‐BJP is found to be effective within a distance smaller than 5° . After post‐processing, the prominent underestimation is efficiently corrected with Bias near 0. RMSE is markedly reduced to be smaller than 2.5 ° C . The post‐processed ERA‐5 and GLDAS‐2.1 are as accurate as ERA‐Interim, but able to provide more detailed information for extreme events due to their finer spatial resolution. Thus, ERA‐5 and GLDAS‐2.1 are more recommended to represent air temperature in the TP. Snow depth as complementary reference data is able to present spatial variance of air temperature. Our study can help alleviate the problem of sparse air temperature data over the TP.

Assembly of Satsuma mandarin mitochondrial genome and identification of cytoplasmic male sterility–specific ORFs in a somatic cybrid of pummelo - Shuai Zhang; Zhao-Ping Yin; Xiao-Meng Wu; Chao-Chao Li; Kai-Dong Xie; Xiu-Xin Deng; Jude W. Grosser; Wen-Wu Guo (Tree Genetics & Genomes, 2020)

Localization and characterization of Citrus centromeres by combining half-tetrad analysis and CenH3-associated sequence profiling - Qiang-Ming Xia; Lu-Ke Miao; Kai-Dong Xie; Zhao-Ping Yin; Xiao-Meng Wu; Chun-Li Chen; Jude W. Grosser; Wen-Wu Guo (Plant Cell Reports, 2020)

Pathogenic characterization of Aeromonas salmonicida subsp. masoucida turbot isolate from China - Ping Wang; Jie Li; Tian Tian He; Nan Li; Zhao Lan Mo; Pin Nie; Hai Xia Xie (Journal of Fish Diseases, 2020)
Aeromonas salmonicida is a gram‐negative bacterium that is the causative agent of furunculosis. An A. salmonicida strain was isolated from diseased turbot ( Scophthalmus maximus ) with the sign of furunculosis from North China. Based on vapA gene, the strain was further classified as A. salmonicida subsp. masoucida RZ6S‐1. Culturing RZ6S‐1 strain at high temperature (28°C) obtained the virulence attenuated strain RZ6S. Genome sequence comparison between the two strains revealed the loss of the type IV secretion system (T4SS) and type III secretion system (T3SS) from the native plasmid pAsmB‐1 and pAsmC‐1 of wild‐type strain RZ6S‐1, respectively. Further study demonstrated that the wild‐type strain RZ6S‐1, but not its derivative mutant RZ6S, can stimulate apoptosis. Elevated protein level of cleaved caspase‐3 was detected from epithelioma papulosum cyprinid (EPC) cells infected with wild‐type strain RZ6S‐1 as compared with that infected with RZ6S strain. Meanwhile, the invasion of the mutant strain RZ6S was about 17‐fold higher than the wild‐type strain RZ6S‐1, suggesting that some protein(s) from A. salmonicida subsp. masoucida RZ6S‐1 suppress its invasion. The RZ6S mutant strain was attenuated, since its LD 50 is over 10,000 times higher compared to the wild‐type strain as revealed in the turbot infection model.

Sandstorm weather is a risk factor for mortality in ischemic heart disease patients in the Hexi Corridor, northwestern China - Xinghui Li; Hui Cai; Xiaolan Ren; Jin He; Jia Tang; Ping Xie; Nan Wang; Fangfei Nie; Linfeng Lei; Chenchen Wang; Wenli Li; Jing Ma (Environmental Science and Pollution Research, 2020)

Structural features of an acidic polysaccharide with the potential of promoting osteoblast differentiation from Lycium ruthenicum Murr. - Shu-Qi Wang; Bing Liu; Su Liu; Song-Zi Xie; Li-Hua Pan; Xue-Qiang Zha; Qiang-Ming Li; Jian-Ping Luo (Natural Product Research, 2020)

Identification and fine mapping of spot blotch (Bipolaris sorokiniana) resistance gene Sb4 in wheat - Panpan Zhang; Guanghao Guo; Qiuhong Wu; Yongxing Chen; Jingzhong Xie; Ping Lu; Beibei Li; Lingli Dong; Miaomiao Li; Rongge Wang; Chengguo Yuan; Huaizhi Zhang; et al. (Theoretical and Applied Genetics, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Biological Aerosol Particles in Polluted Regions - Wei Hu; Zihan Wang; Shu Huang; Lujie Ren; Siyao Yue; Ping Li; Qiaorong Xie; Wanyu Zhao; Lianfang Wei; Hong Ren; Libin Wu; Junjun Deng; et al. (Current Pollution Reports, 2020)

The implications of hippocampal neurogenesis in adolescent rats after status epilepticus: a novel role of notch signaling pathway in regulating epileptogenesis - Ping Yuan; Wei Han; Lingling Xie; Li Cheng; Hengsheng Chen; Jin Chen; Li Jiang (Cell and Tissue Research, 2020)

Regulatory mechanisms and therapeutic potential of microglial inhibitors in neuropathic pain and morphine tolerance - Er-rong Du; Rong-ping Fan; Li-lou Rong; Zhen Xie; Chang-shui Xu (Journal of Zhejiang University-SCIENCE B, 2020)

Relative energy zero ratio-based approach for identifying pulse-like ground motions - Ping Liu; Ning Li; Hua Ma; Lili Xie; Baofeng Zhou (Earthquake Engineering and Engineering Vibration, 2020)

The complete chloroplast genome of the daimyo oak, Quercus dentata Thunb. - Hua-Lei Hu; Jing-Yu Zhang; Yu-Ping Li; Lu Xie; Dong-Bin Chen; Qun Li; Yan-Qun Liu; Shu-Rong Hui; Li Qin (Conservation Genetics Resources, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Pharmacokinetic study of imrecoxib in patients with renal insufficiency - Qi Pei; Jin-lian Xie; Jie Huang; Wen-yu Liu; Xiao-yan Yang; Yan Wang; Wei Li; Hong-yi Tan; Hao Zhang; Guo-Ping Yang (European Journal of Clinical Pharmacology, 2019)

Genome-wide association analysis of salt tolerance QTLs with SNP markers in maize (Zea mays L.) - Yonghong Xie; Yan Feng; Qi Chen; Feike Zhao; Shuijuan Zhou; Ying Ding; Xianliang Song; Ping Li; Baohua Wang (Genes & Genomics, 2019)

Exploring the Potential of Mesoporous Silica as a Carrier for Puerarin: Characterization, Physical Stability, and In Vivo Pharmacokinetics - Zhi Wang; Bei-Ni Ye; Yong-Tai Zhang; Jian-Xu Xie; Wan-Si Li; Hong-Tao Zhang; Ying Liu; Nian-Ping Feng (AAPS PharmSciTech, 2019)

Assessment of slope construction risk uncertainty based on index importance ranking - Daming Lin; Ping Chen; Jilei Ma; Yun Zhao; Tao Xie; Renmao Yuan; Lin Li (Bulletin of Engineering Geology and the Environment, 2019)

A novel astrovirus identified in wild rhesus monkey feces in China - Yun-yun Xin; Li-li Li; Yuan-yun Ao; Zhi-ping Xie; Jin-song Li; Zhao-jun Duan; Jie-mei Yu; Bing Zhang (Archives of Virology, 2019)

Effect of Interaction between Adenosine and Nitric Oxide on Central Nervous System Oxygen Toxicity - Cheng-wei Xie; Zhong-zhuang Wang; Ya-nan Zhang; Yu-liang Chen; Run-ping Li; Jun-dong Zhang (Neurotoxicity Research, 2019)

Molecular properties and immunomodulatory activities of a water-soluble heteropolysaccharide isolated from Plantago asiatica L. leaves - Jun-Yi Yin; Xin-Yue Huang; Li Wang; Jian-Qi Guo; Ming-Yong Xie; Jian-Yong Wu; Shao-Ping Nie (Natural Product Research, 2019)

Influence of permeation effect on the microfabric of the slip zone soils: A case study from the Huangtupo landslide - Fa-sheng Miao; Yi-ping Wu; Yuan-hua Xie; Lin-wei Li; Jie Li; Lei Huang (Journal of Mountain Science, 2019)

Effects of glyphosate on soybean metabolism in strains bred for glyphosate-resistance - Wei-yu Li; Ping Lu; Hao Xie; Gui-quan Li; Jing-xuan Wang; Dong-yu Guo; Xing-yu Liang (Physiology and Molecular Biology of Plants, 2019)

Microsatellite records for volume 11, issue 1 - Da-Qing Chen; Zaijie Dong; Min Fang; Jianjun Fu; Xiang-Yang Jia; Bingjie Jiang; Jingmiao Li; Qingqing Li; Suhui Liao; Ping Liu; Yulin Liu; Guocheng Shu; et al. (Conservation Genetics Resources, 2019)

Impact of surfactant and dissolved organic matter on uptake of atrazine in maize and its mobility in soil - Bing Bing Tian; Jing Hua Zhou; Fei Xie; Qian Nan Guo; Ai Ping Zhang; Xin Qiang Wang; Qian Qian Yu; Na Li; Hong Yang (Journal of Soils and Sediments, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

ENSO forced and local variability of North Tropical Atlantic SST: model simulations and biases - Yun Yang; Shang-Ping Xie; Lixin Wu; Yu Kosaka; Jianping Li (Climate Dynamics, 2018)

Effects of cadmium stress on the antioxidant system and chlorophyll fluorescence characteristics of two Taxodium clones - Ying-Li Ma; Hui-Fang Wang; Ping Wang; Chao-Guang Yu; Si-Qian Luo; Yu-Feng Zhang; Yin-Feng Xie (Plant Cell Reports, 2018)

New method for revealing dislocations in garnet: premelting decoration - Xiangwen Liu; Zhanjun Xie; Zhenmin Jin; Zhuoyue Li; Ping Ao; Yikun Wu (Physics and Chemistry of Minerals, 2018)

A New Advance Classification Method for Surrounding Rock in Tunnels Based on the Set-Pair Analysis and Tunnel Seismic Prediction System - Lin Bu; Shu-cai Li; Shao-shuai Shi; Xiao-kun Xie; Li-ping Li; Zong-qing Zhou; Zhi-jie Wen (Geotechnical and Geological Engineering, 2018)

Repaglinide-irbesartan drug interaction: effects of SLCO1B1 polymorphism on repaglinide pharmacokinetics and pharmacodynamics in Chinese population - Qi Pei; Jun-Yan Liu; Ji-Ye Yin; Guo-Ping Yang; Shi-Kun Liu; Yi Zheng; Pan Xie; Cheng-Xian Guo; Mi Luo; Hong-Hao Zhou; Xi Li; Zhao-Qian Liu (European Journal of Clinical Pharmacology, 2018)

Application of Phragmites australis to remove phenol from aqueous solutions by chemical activation in batch and fixed-bed columns - Sheng-Li Shi; Jun-Ping Lv; Qi Liu; Fang-Ru Nan; Xiao-Yan Jiao; Jia Feng; Shu-Lian Xie (Environmental Science and Pollution Research, 2018)

Collapse behavior and microstructural evolution of loess soils from the Loess Plateau of China - Wan-li Xie; Ping Li; Mao-sheng Zhang; Tian-e Cheng; Yong Wang (Journal of Mountain Science, 2018)

BDNF/TrkB Pathway Mediates the Antidepressant-Like Role of H2S in CUMS-Exposed Rats by Inhibition of Hippocampal ER Stress - Le Wei; Li-Yuan Kan; Hai-Ying Zeng; Yi-Yun Tang; Hong-Lin Huang; Ming Xie; Wei Zou; Chun-Yan Wang; Ping Zhang; Xiao-Qing Tang (NeuroMolecular Medicine, 2018)

Genome-wide identification and evolution of TC1/Mariner in the silkworm (Bombyx mori) genome - Li-Qin Xie; Ping-Lan Wang; Shen-Hua Jiang; Ze Zhang; Hua-Hao Zhang (Genes & Genomics, 2018)

Temporal patterns and processes of genetic differentiation of the Brachionus calyciflorus (Rotifera) complex in a subtropical shallow lake - Ye Zhang; Ao Zhou; Yi-Long Xi; Qiang Sun; Le-Feng Ning; Ping Xie; Xin-Li Wen; Xian-Ling Xiang (Hydrobiologia, 2018)

Mycobacterium tuberculosis Major Facilitator Superfamily Transporters - Ping Li; Yinzhong Gu; Jiang Li; Longxiang Xie; Xue Li; Jianping Xie (The Journal of Membrane Biology, 2017)

Atlantic effects on recent decadal trends in global monsoon - Youichi Kamae; Xichen Li; Shang-Ping Xie; Hiroaki Ueda (Climate Dynamics, 2017)

Mapping stripe rust resistance gene YrZH22 in Chinese wheat cultivar Zhoumai 22 by bulked segregant RNA-Seq (BSR-Seq) and comparative genomics analyses - Yong Wang; Jingzhong Xie; Huaizhi Zhang; Bingmin Guo; Shunzong Ning; Yongxing Chen; Ping Lu; Qiuhong Wu; Miaomiao Li; Deyun Zhang; Guanghao Guo; Yan Zhang; et al. (Theoretical and Applied Genetics, 2017)

Hydrogen Peroxide and Strigolactones Signaling Are Involved in Alleviation of Salt Stress Induced by Arbuscular Mycorrhizal Fungus in Sesbania cannabina Seedlings - Cun-Cui Kong; Cheng-Gang Ren; Run-Zhi Li; Zhi-Hong Xie; Ji-Ping Wang (Journal of Plant Growth Regulation, 2017)

Cu Removal from Acid Mine Drainage by Modified Pyrite: Batch and Column Experiments - Yan Yang; Tianhu Chen; Ping Li; Qiaoqin Xie; Xinmin Zhan (Mine Water and the Environment, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Prolonged exposure to low-dose microcystin induces nonalcoholic steatohepatitis in mice: a systems toxicology study - Jun He; Guangyu Li; Jun Chen; Juan Lin; Cheng Zeng; Jing Chen; Junliang Deng; Ping Xie (Archives of Toxicology, 2017)

Identification and Characterization of the Lysine-Rich Matrix Protein Family in Pinctada fucata: Indicative of Roles in Shell Formation - Jian Liang; Jun Xie; Jing Gao; Chao-Qun Xu; Yi Yan; Gan-Chu Jia; Liang Xiang; Li-Ping Xie; Rong-Qing Zhang (Marine Biotechnology, 2016)

Effects of excessive equatorial cold tongue bias on the projections of tropical Pacific climate change. Part I: the warming pattern in CMIP5 multi-model ensemble - Gen Li; Shang-Ping Xie; Yan Du; Yiyong Luo (Climate Dynamics, 2016)

Polymorphisms in complement genes and risk of preeclampsia in Taiyuan, China - Weiwei Wu; Hailan Yang; Yongliang Feng; Ping Zhang; Shuzhen Li; Xin Wang; Tingting Peng; Fang Wang; Bingjie Xie; Pengge Guo; Mei Li; Ying Wang; et al. (Inflammation Research, 2016)

Advances on Bioactive Polysaccharides from Medicinal Plants - Jian-Hua Xie; Ming-Liang Jin; Gordon A. Morris; Xue-Qiang Zha; Han-Qing Chen; Yang Yi; Jing-En Li; Zhi-Jun Wang; Jie Gao; Shao-Ping Nie; Peng Shang; Ming-Yong Xie (Critical Reviews in Food Science and Nutrition, 2016)

Effect of CO 2 on Chemical and Microbial Changes of Pacific White Shrimp During Modified Atmosphere Packaging - Yun-Fang Qian; Jing Xie; Sheng-Ping Yang; Wen-Hui Wu; Qing Xiong; Zhi-Li Gao; Jian-Bing Shi (Journal of Aquatic Food Product Technology, 2016)

Two new glycosides isolated from Sapindus mukorossi fruits: effects on cell apoptosis and caspase-3 activation in human lung carcinoma cells - Xuan-Ming Zhang; De-Po Yang; Zhi-Yong Xie; Qing Li; Long-Ping Zhu; Zhi-Min Zhao (Natural Product Research, 2016)

Neuropeptide S ameliorates olfactory spatial memory impairment induced by scopolamine and MK801 through activation of cognate receptor-expressing neurons in the subiculum complex - Yu-Feng Shao; Can Wang; Jun-Fan Xie; Xiang-Pan Kong; Le Xin; Chao-Yu Dong; Jing Li; Wen-Ting Ren; Yi-Ping Hou (Brain Structure and Function, 2016)

Fine genetic mapping of spot blotch resistance gene Sb3 in wheat (Triticum aestivum) - Ping Lu; Yong Liang; Delin Li; Zhengzhong Wang; Wenbin Li; Guoxin Wang; Yong Wang; Shenghui Zhou; Qiuhong Wu; Jingzhong Xie; Deyun Zhang; Yongxing Chen; et al. (Theoretical and Applied Genetics, 2016)

Erratum to: Quantitatively evaluating detoxification of the hepatotoxic microcystin-LR through the glutathione (GSH) pathway in SD rats - Xiaochun Guo; Liang Chen; Jun Chen; Ping Xie; Shangchun Li; Jun He; Wei Li; Huihui Fan; Dezhao Yu; Cheng Zeng (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Quantitatively evaluating detoxification of the hepatotoxic microcystin-LR through the glutathione (GSH) pathway in SD rats - Xiaochun Guo; Liang Chen; Jun Chen; Ping Xie; Shangchun Li; Jun He; Wei Li; Huihui Fan; Dezhao Yu; Cheng Zeng (Environmental Science and Pollution Research, 2015)

Brassinosteroid alleviates chilling-induced oxidative stress in pepper by enhancing antioxidation systems and maintenance of photosystem II - Jie Li; Ping Yang; Yantai Gan; Jihua Yu; Jianming Xie (Acta Physiologiae Plantarum, 2015)

p55γ functional mimetic peptide N24 blocks vascular proliferative disorders - Jiaojiao Guo; Ning Xie; Geng Li; Yan Zhang; Fengxiang Lv; Sile Guo; Yuanqing Feng; Chun-Mei Cao; Rui-Ping Xiao (Journal of Molecular Medicine, 2015)

The ductility-based strength reduction factor for the mainshock–aftershock sequence-type ground motions - Chang-Hai Zhai; Wei-Ping Wen; Shuang Li; Li-Li Xie (Bulletin of Earthquake Engineering, 2015)

A Novel Oral Preparation of Hydroxysafflor Yellow A Base on a Chitosan Complex: A Strategy to Enhance the Oral Bioavailability - Guan-nan Ma; Fang-lin Yu; Shan Wang; Zhi-ping Li; Xiang-yang Xie; Xing-guo Mei (AAPS PharmSciTech, 2015)

P5-2 of rice black-streaked dwarf virus is a non-structural protein targeted to chloroplasts - Xiao-Ya Liu; Jian Yang; Li Xie; Jing Li; Xi-Jiao Song; Jian-Ping Chen; Heng-Mu Zhang (Archives of Virology, 2015)

Association between the CYP1A2 polymorphisms and risk of cancer: a meta-analysis - Wen-Xia Sun; Ying-Hua Chen; Zhi-Zhong Liu; Jian-Jun Xie; Wei Wang; Ya-Ping Du; Yu Chen; Xu-Liang Shen; Xiao-Feng He; Li-Xia Wu; Wu Wei; Lin Zhang (Molecular Genetics and Genomics, 2015)

Mitochondrial estrogen receptor β inhibits cell apoptosis via interaction with Bad in a ligand-independent manner - Jiayi Liang; Qiang Xie; Ping Li; Xueyun Zhong; Yunxian Chen (Molecular and Cellular Biochemistry, 2015)

Potential sources of and ecological risks from heavy metals in agricultural soils, Daye City, China - Ping Du; Yunfeng Xie; Shijie Wang; Huanhuan Zhao; Zhuo Zhang; Bin Wu; Fasheng Li (Environmental Science and Pollution Research, 2015)

Impact of MDM2 Single Nucleotide Polymorphism on Oral Squamous Cell Carcinoma Risk - Jian-Li Xie; Jing-Lei Yang; De-Sheng Liu; Yong-Gang Xie; Ping Ji (Cell Biochemistry and Biophysics, 2015)

Characterization of homologous and heterologous interactions between viroplasm proteins P6 and P9-1 of the fijivirus southern rice black-streaked dwarf virus - Jing Li; Jin Xue; Heng-Mu Zhang; Jian Yang; Li Xie; Jian-Ping Chen (Archives of Virology, 2015)

Different secondary metabolic responses to MeJA treatment in shikonin-proficient and shikonin-deficient cell lines from Arnebia euchroma (Royle) Johnst - Sheng Wang; Lan Ping Guo; Teng Xie; Jian Yang; Jin Fu Tang; Xuan Li; Xiao Wang; Lu Qi Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Isolation and molecular characterization of an ethylene response factor NtERF1-1 in Nicotiana tabacum cv. Xanthi - Jun-Shan Gao; Li Hu; Peng Xie; Yan Meng; Yong-Ping Cai; Yi Lin (Journal of Biosciences, 2014)

Secretory expression of a bispecific antibody targeting tumor necrosis factor and ED-B fibronectin in Pichia pastoris and its functional analysis - Meng-yuan Liu; Xue-ping Hu; Mian Xie; Si-jing Jiang; Lu-jun Li; Dong-xu Liu; Xiao-song Yang (Biotechnology Letters, 2014)

Erratum to: Identification of a novel mutation in a Chinese family with Nance-Horan syndrome by whole exome sequencing - Nan Hong; Yan-hua Chen; Chen Xie; Bai-sheng Xu; Hui Huang; Xin Li; Yue-qing Yang; Ying-ping Huang; Jian-lian Deng; Ming Qi; Yang-shun Gu (Journal of Zhejiang University-SCIENCE B, 2014)

Indian Ocean variability in the CMIP5 multi-model ensemble: the zonal dipole mode - Lin Liu; Shang-Ping Xie; Xiao-Tong Zheng; Tim Li; Yan Du; Gang Huang; Wei-Dong Yu (Climate Dynamics, 2014)

Assessment of dietary phytoestrogen intake via plant-derived foods in China - Xiao Juan Hu; Wan Rui Song; Li Ying Gao; Shao Ping Nie; Gerhard Eisenbrand; Ming Yong Xie (Food Additives & Contaminants: Part A, 2014)

Comparative genetic mapping and genomic region collinearity analysis of the powdery mildew resistance gene Pm41 - Zhenzhong Wang; Yu Cui; Yongxing Chen; Deyun Zhang; Yong Liang; Dong Zhang; Qiuhong Wu; Jingzhong Xie; Shuhong Ouyang; Delin Li; Yinlian Huang; Ping Lu; et al. (Theoretical and Applied Genetics, 2014)

Identification of a novel mutation in a Chinese family with Nance-Horan syndrome by whole exome sequencing - Nan Hong; Yan-hua Chen; Chen Xie; Bai-sheng Xu; Hui Huang; Xin Li; Yue-qing Yang; Ying-ping Huang; Jian-lian Deng; Ming Qi; Yang-shun Gu (Journal of Zhejiang University-SCIENCE B, 2014)

Chemical composition, antimicrobial and antioxidant activities of essential oil from Ampelopsis megalophylla - Xian-Fei Xie; Jian-Wu Wang; Han-Ping Zhang; Qi-Xiong Li; Bang-Yin Chen (Natural Product Research, 2014)

Sequence and phylogenetic analysis of surface protein genes of emerging H9N2 influenza viruses isolated from poultry in two geographical regions of China - Yu Xue; Jing-Lan Wang; Zhuan-Qiang Yan; Guang-Wei Li; Shun-Yan Chen; Xiang-Bin Zhang; Jian-Ping Qin; Hai-Yan Li; Shuang Chang; Feng Chen; Ying-Zuo Bee; Qing-Mei Xie (Virus Genes, 2014)

Structure-based design, synthesis, and anticonvulsant activity of isatin-1-N-phenylacetamide derivatives - Chao Xie; Li-Ming Tang; Fu-Nan Li; Li-Ping Guan; Cheng-Yan Pan; Si-Hong Wang (Medicinal Chemistry Research, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Rice black-streaked dwarf virus genome segment S5 is a bicistronic mRNA in infected plants - Jian Yang; Heng-Mu Zhang; Lu Ying; Jing Li; Ming-Fang Lv; Li Xie; Pei-Pei Li; Xiao-Ya Liu; Dai Liang-Ying; Jian-Ping Chen (Archives of Virology, 2014)

Comparative Study of Different Latent Infections of Herpes Simplex Virus Type I in a Murine Model - Wen Huang; Ping Zhao; Xiao Chen; Ping Li; Gaonian Zhao; Mingming Xu; Xiuying Chen; Peng Xie (Cell Biochemistry and Biophysics, 2014)

Adenosine Monophosphate Affects Competence Development and Plasmid DNA Transformation in Escherichia coli - Yan Zhang; Wenhua Li; Liming Wang; Ping Shen; Zhixiong Xie (Current Microbiology, 2013)

Identification and Expression Profiles of IL-8 in Bighead Carp (Aristichthys nobilis) in Response to Microcystin-LR - Huiying Li; Yan Cai; Ping Xie; Guangyu Li; Le Hao; Qian Xiong (Archives of Environmental Contamination and Toxicology, 2013)

Population persistence of a Tertiary relict tree Tetracentron sinense on the Ailao Mountains, Yunnan, China - Cindy Q. Tang; Ming-Chun Peng; Long-Yuan He; Masahiko Ohsawa; Chong-Yun Wang; Tian-Hua Xie; Wen-Shun Li; Jia-Ping Li; Hong-Yu Zhang; Yong Li; Xian-Ming Yang; Guo-Song Li (Journal of Plant Research, 2013)

Identification and characterization of antifungal active substances of Streptomyces hygroscopicus BS-112 - Nan Zhang; Zhen Song; Yuhua Xie; Ping Cui; Hongxia Jiang; Tao Yang; Ruicheng Ju; Yuhua Zhao; Jinyu Li; Xunli Liu (World Journal of Microbiology and Biotechnology, 2013)

Interactions between the P6 and P5-1 proteins of southern rice black-streaked dwarf fijivirus in yeast and plant cells - Jing Li; Jin Xue; Heng-Mu Zhang; Jian Yang; Ming-Fang Lv; Li Xie; Yuan Meng; Pei-Pei Li; Jian-Ping Chen (Archives of Virology, 2013)

Molecular characterization and phylogenetic analysis of infectious bursal disease viruses isolated from chicken in South China in 2011 - Di Liu; Xiang-Bin Zhang; Zhuan-Qiang Yan; Feng Chen; Jun Ji; Jian-Ping Qin; Hai-Yan Li; Jun-Peng Lu; Yu Xue; Jia-Jia Liu; Qing-Mei Xie; Jing-Yun Ma; et al. (Tropical Animal Health and Production, 2013)

Acute pancreatitis associated left-sided portal hypertension with severe gastrointestinal bleeding treated by transcatheter splenic artery embolization: a case report and literature review - Zhi-yu Li; Bin Li; Yu-lian Wu; Qiu-ping Xie (Journal of Zhejiang University-SCIENCE B, 2013)

Dietary consumption and diet diversity and risk of developing bladder cancer: results from the South and East China case–control study - Fatima Isa; Li-Ping Xie; Zhiquan Hu; Zhaohui Zhong; Marjolein Hemelt; Raoul C. Reulen; Y. C. Wong; Po-Chor Tam; Kai Yang; Chao Chai; Xing Zeng; Yilan Deng; et al. (Cancer Causes & Control, 2013)

Paracoccus siganidrum sp. nov., isolated from fish gastrointestinal tract - Ying Liu; Qing-yi Xie; Kui Hong; Lei Li; Ya-mei Zhao; Yi-li Tang; Jun-ying An; Ping-ping Zhu; Chun-hou Xu (Antonie van Leeuwenhoek, 2013)

Human anti-EGFL7 recombinant full-length antibodies selected from a mammalian cell-based antibody display library - Feng Li; Yan-Hong Liu; Yan-Wen Li; Qian Ju; Lin Chen; Ping-Li Xie; Yue-Hui Li; Guan-Cheng Li (Molecular and Cellular Biochemistry, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Genetic Overlap in the Quantitative Resistance of Rice at the Seedling and Adult Stages to Xanthomonas oryzae pv. oryzae - Yong-Li Zhou; Xue-Wen Xie; Mei-Rong Xu; Jin-Ping Zang; Ling-Hua Zhu; Jian-Long Xu; Zhi-Kang Li (Journal of Plant Biology, 2012)

Role of RhoA/ROCK Signaling in Endothelial-Monocyte-Activating Polypeptide II Opening of the Blood–Tumor Barrier - Hui Xie; Yi-xue Xue; Li-bo Liu; Yun-hui Liu; Ping Wang (Journal of Molecular Neuroscience, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Protein sequence analysis based on hydropathy profile of amino acids - Xiao-li Xie; Li-fei Zheng; Ying Yu; Li-ping Liang; Man-cai Guo; John Song; Zhi-fa Yuan (Journal of Zhejiang University-SCIENCE B, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Genetic structure of three fosmid‐fragments encoding 16S rRNA genes of the Miscellaneous Crenarchaeotic Group (MCG): implications for physiology and evolution of marine sedimentary archaea - Ping‐Yi Li; Bin‐Bin Xie; Xi‐Ying Zhang; Qi‐Long Qin; Hong‐Yue Dang; Xu‐Min Wang; Xiu‐Lan Chen; Jun Yu; Yu‐Zhong Zhang (Environmental Microbiology, 2012)
Summary Archaea of the Miscellaneous Crenarchaeotic Group (MCG) exist widely in soil, freshwater and marine sediments of both surface and subsurface. However, current knowledge about this group is limited to its phylogenetic diversity. An archaeal 16S library was constructed from a sediment sample from the South China Sea, which was dominated by MCG and Marine Group I (MG‐I). A metagenomic library was constructed from the same sediment sample, and three MCG fosmids (E6‐3G, E37‐7F and E48‐1C) containing 16S rRNA genes were screened. Annotation showed that the three genomic fragments encode a variety of open reading frames (ORFs) that are potentially homologous to important functional genes related to lipid biosynthesis, energy metabolism, and resistance to oxidants. No colinear regions were found between MCG fosmids and reported archaeal genomic fragments or genomes, suggesting that the MCG archaea are quite different from the sequenced archaea in gene arrangement. Analyses of both the phylogenies of 16S rRNA genes and several informational processing genes and nucleotide frequencies showed that MCG archaea are distinct from MG‐I plus relatives. In addition, tetranucleotide frequency analysis in combination with phylogenetic analysis suggested that some fragments in the MCG fosmids are probably derived from non‐MCG or non‐archaeal genomes.

Inhibition of Intercellular Adhesion in Herpex Simplex Virus Infection by Glycyrrhizin - Wen Huang; Xiao Chen; Qi Li; Ping Li; Gaonian Zhao; Mingming Xu; Peng Xie (Cell Biochemistry and Biophysics, 2012)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

The Influence of Stress Factors on the Reactivation of Latent Herpes Simplex Virus Type 1 in Infected Mice - Wen Huang; Peng Xie; Mingming Xu; Ping Li; Gaonian Zao (Cell Biochemistry and Biophysics, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Receptor signaling in immune cell development and function - Xiao-Ping Zhong; Jinwook Shin; Balachandra K. Gorentla; Tommy O’Brien; Sruti Srivatsan; Li Xu; Yong Chen; Danli Xie; Hongjie Pan (Immunologic Research, 2011)

Blood cells of a sisorid catfish Glyptosternum maculatum (Siluriformes: Sisoridae), in Tibetan Plateau - Hui Juan Zhang; Cong Xin Xie; Da Peng Li; Hai Ping Liu; Xue Feng Yang (Fish Physiology and Biochemistry, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Localized expression pattern of miR-184 in Drosophila - Ping Li; Jianjian Peng; Jiangbo Hu; Zhongxin Xu; Wei Xie; Liudi Yuan (Molecular Biology Reports, 2011)

Water quality of a tributary of the Pearl River, the Beijiang, Southern China: implications from multivariate statistical analyses - Ming W. Song; Ping Huang; Feng Li; Hui Zhang; Kai Z. Xie; Xi H. Wang; Guo X. He (Environmental Monitoring and Assessment, 2011)

Proteomics analysis of plasma membrane from liver sinusoidal endothelial cells after partial hepatectomy by an improved two-dimensional electrophoresis - Xuanwen Li; Li Xiong; Chunliang Xie; Jia Cao; Huobao Deng; Yong Lin; Rui Cao; Jianglin Li; Ping Chen; Songping Liang (Molecular and Cellular Biochemistry, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Regulating A549 cells growth by ASO inhibiting miRNA expression - Ping-Yu Wang; You-Jie Li; Shuai Zhang; Zun-Ling Li; Zhen Yue; Ning Xie; Shu-Yang Xie (Molecular and Cellular Biochemistry, 2010)

Antioxidant response in liver of the phytoplanktivorous bighead carp (Aristichthys nobilis) intraperitoneally-injected with extracted microcystins - Li Li; Ping Xie; Longgen Guo (Fish Physiology and Biochemistry, 2010)

Ubiquitin ligase Smurf1 targets TRAF family proteins for ubiquitination and degradation - Shan Li; Kefeng Lu; Jian Wang; Liguo An; Guiwen Yang; Hui Chen; Yu Cui; Xiushan Yin; Ping Xie; Guichun Xing; Fuchu He; Lingqiang Zhang (Molecular and Cellular Biochemistry, 2010)

Water and sediment chemistry of Lake Pumayum Co, South Tibet, China: implications for interpreting sediment carbonate - Jianting Ju; Li-ping Zhu; Junbo Wang; Manping Xie; Xiaolin Zhen; Yong Wang; Ping Peng (Journal of Paleolimnology, 2010)

A new dinorclerone diterpenoid glycoside from Tinospora sinensis - Lang-Ping Dong; Chang-Xiang Chen; Wei Ni; Bai-Bo Xie; Jun-Zhu Li; Hai-Yang Liu (Natural Product Research, 2010)

Diatom community succession in the recent history of a eutrophic Yunnan Plateau lake, Lake Dianchi, in subtropical China - Zhi-jun Gong; Yan-ling Li; Ji Shen; Ping Xie (Limnology, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Epigallocatechin-3-gallate enhances ischemia/reperfusion-induced apoptosis in human umbilical vein endothelial cells via AKT and MAPK pathways - Tianpeng Zhang; Dan Yang; Yongna Fan; Ping Xie; Huihua Li (Apoptosis, 2009)

A novel triple-regulated oncolytic adenovirus carrying PDCD5 gene exerts potent antitumor efficacy on common human leukemic cell lines - Min Xie; Ji-Hong Niu; Yan Chang; Qi-Jun Qian; Hong-Ping Wu; Lin-Fang Li; Yao Zhang; Jin-Lan Li; Xiao-Jun Huang; Guo-Rui Ruan (Apoptosis, 2009)

Assessment effects of cage culture on nitrogen and phosphorus dynamics in relation to fallowing in a shallow lake in China - Longgen Guo; Zhongjie Li; Ping Xie; Leyi Ni (Aquaculture International, 2009)

Molecular Cloning, Expression, and Chromosomal Mapping of the Porcine CDC-2-Like Kinase 1 (CLK1) Gene - Shui Hua Xie; Jia Qi Li; Yao Sheng Chen; Ping Gao; Hao Zhang; Ze Yue Li (Biochemical Genetics, 2009)

Physiological Stress of High NH 4 + Concentration in Water Column on the Submersed Macrophyte Vallisneria Natans L. - Te Cao; Ping Xie; Zhongqiang Li; Leyi Ni; Meng Zhang; Jun Xu (Bulletin of Environmental Contamination and Toxicology, 2009)

Determination of soluble solid content and acidity of loquats based on FT-NIR spectroscopy - Xia-ping Fu; Jian-ping Li; Ying Zhou; Yi-bin Ying; Li-juan Xie; Xiao-ying Niu; Zhan-ke Yan; Hai-yan Yu (Journal of Zhejiang University-SCIENCE B, 2009)

Plasma biochemical responses of the omnivorous crucian carp (Carassius auratus) to crude cyanobacterial extracts - Xuezhen Zhang; Ping Xie; Weimin Wang; Dapeng Li; Zechao Shi (Fish Physiology and Biochemistry, 2008)

Proteasome-dependent inactivation of Akt is essential for 12-O-tetradecanoylphorbol 13-acetate-induced apoptosis in vascular smooth muscle cells - Yongna Fan; Ping Xie; Hua Zhang; Shubin Guo; Dongfeng Gu; Mingpeng She; HuiHua Li (Apoptosis, 2008)

Responses to air temperature and soil moisture of growth of four dominant species on sand dunes of central Inner Mongolia - Yuanrun Zheng; Glyn M. Rimmington; Zhixiao Xie; Lei Zhang; Ping An; Guangsheng Zhou; Xiangjun Li; Yunjiang Yu; Lijun Chen; Hideyuki Shimizu (Journal of Plant Research, 2008)

Application of NIR spectroscopy for firmness evaluation of peaches - Xia-ping FU; Yi-bin Ying; Ying Zhou; Li-juan Xie; Hui-rong Xu (Journal of Zhejiang University-SCIENCE B, 2008)

Involvement of GlnK, a PII protein, in control of nitrogen fixation and ammonia assimilation in Pseudomonas stutzeri A1501 - Sheng He; Ming Chen; Zhihong Xie; Yongliang Yan; Hongquan Li; Ying Fan; Shuzhen Ping; Min Lin; Claudine Elmerich (Archives of Microbiology, 2008)

A Novel Glycosylphosphatidylinositol-Anchored Alkaline Phosphatase Dwells in the Hepatic Duct of the Pearl Oyster, Pinctada fucata - Li-Ping Xie*; Yuan-Tai Wu*; Yi-Ping Dai; Qing Li; Rong-Qing Zhang (Marine Biotechnology, 2007)

Across Genus Plasmid Transformation Between Bacillus subtilis and Escherichia coli and the Effect of Escherichia coli on the Transforming Ability of Free Plasmid DNA - Xiaojuan Wang; Meiju Li; Qing Yan; Xiangdong Chen; Jing Geng; Zhixiong Xie; Ping Shen (Current Microbiology, 2007)

Apelin suppresses apoptosis of human osteoblasts - Hui Xie; Ling-Qing Yuan; Xiang-Hang Luo; Jiao Huang; Rong-Rong Cui; Li-Juan Guo; Hou-De Zhou; Xian-Ping Wu; Er-Yuan Liao (Apoptosis, 2007)

Land-cover changes in an urban lake watershed in a mega-city, Central China - Yan Li; Shuqing Zhao; Kun Zhao; Ping Xie; Jingyun Fang (Environmental Monitoring and Assessment, 2006)

Relationships between fractionations of Pb, Cd, Cu, Zn and Ni and soil properties in urban soils of Changchun, China - Ping Guo; Zhong-lei Xie; Jun Li; Chun-li Kang; Jian-hua Liu (Chinese Geographical Science, 2005)

The genetic basis of Cowden's syndrome: three novel mutations in PTEN/MMAC1/TEP1 - H. C. Tsou; Xiao Li Ping; Xiao Xun Xie; Alexandra C. Gruener; Hong Zhang; R. Nini; Karen Swisshelm; Virginia Sybert; Terry M. Diamond; Rebecca Sutphen; M. Peacocke (Human Genetics, 1998)